GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2015)
A dataset containing 364227743 species occurrences available in GBIF matching the query: TaxonKey: Animalia. The dataset includes 364227743 records from 5805 constituent datasets: 3857 records from Paläontologie Marburg. 7 records from Uferzone Wipper (Biesenrode). 9 records from Zwickau- Schwanenteich. 10 records from Collection Arachnologie fossil - SMF. 240818 records from Bugbase, Lepidopterological Society. 42 records from Stadtbiotop Ulrichteich. 169 records from Vorderer Tiergarten (Dessau). 138 records from Birdrace_MarschPIeper_Pinneberg. 34 records from annex4. 75 records from BIRDRACE Die Kartoffelsäcke. 47 records from Streuobstwiese Stedar 2008. 15 records from Projeto Abrace o Boto Cinza. 555 records from MVZ Hildebrand Collection (Arctos). 1 records from Ctenophora ZMK. 3 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 33 records from Ökologischer Weinberg (Guntersblum). 21 records from Wir erkunden die Hofau, Klasse 5c. 24 records from Artenvielfalt in der Quälingsbachaue Gladbeck. 22 records from Von der Nutzung zur Natur. 37 records from BUND Naturschutzzentrum St. Julian. 30363 records from CAS Mammalogy (MAM). 9445 records from Invertebrate specimens in the Wakayama Prefectural Museum of Natural History, Japan.. 228 records from (Table 6) Ostracod assemblages of sediment core 9409. 4 records from Ostracoda abundance of Hole 11-105. 56 records from Coarse fraction analysis and texture of biogenous sands from Josephine Seamount surface samples (Table 2). 66 records from Distribution of benthic abyssal gastropods in the Iberian Deep-Sea Basin (Table 2). 8 records from Meiofauna abundance in sediment core 13368-003. 5 records from Benthic macrofauna abundance of sediment core 13077-023. 4957 records from Mamíferos de los Parques Nacionales Lagunas de Montebello y Palenque, Chiapas. 96695 records from Molluscs collection (IM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 3085 records from Faunal Inventory of Morysin Nature Reserve. 15637 records from CCBER Herpetology Collection. 476 records from Caracterización Aves IAI-GAICA: Proyecto Cambio Climático. 48 records from Morphologische Daten von Natrix. 1 records from A new species of Cottunculus (Teleostei: Psychrolutidae) from the Mid Atlantic Ridge.. 60574 records from Ornithology Collection Non Passeriformes - Royal Ontario Museum. 62 records from The North American spider genera Paratheridula, Tekellina, Pholcomma and Archerius (Araneae: Theridiidae). 38955 records from Stuart M. Fullerton Collection of Arthropods (UCFC), University of Central Florida. 6 records from (Table 5) Miocene biostratigraphy of the Langenfeldian and Gramian stages in Schleswig-Holstein. 175 records from Myriapoda & Onychophora collection (MY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 12876 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mollusca_Pectinoidea. 7000 records from CCBER Ornithology Collection. 1150 records from RSPB - Great Yellow Bumblebee sightings data in the UK, 1990 onwards (RSPB, BBCT, HBRG).. 92 records from Type specimens of invertebrate collection at University of Oulu Zoological Museum. 22 records from A synoptic review of the ants of California (Hymenoptera: Formicidae).. 173 records from Conchological Society of Great Britain & Ireland - Mollusc (non-marine): Records of Fossil Molluscs for Great Britain. 28 records from The land crab Johngarthia planata (Stimpson, 1860) (Crustacea, Brachyura, Gecarcinidae) colonizes human-dominated ecosystems in the continental mainland coast of Mexico. 4 records from Spielwiese. 24 records from Trockenrasen Franzigmark (Halle/Saale). 44 records from Naturschutzgebiet Lippeaue (Marl) - Pfadis in Sickingmühle. 8 records from Pomacentrus aurifrons, a new species of damselfish (Pomacentridae) from Melanesia.. 1 records from new species of the fungus-farming ant genus Mycetagroicus Brandao & Mayhe-Nunes A new species of the fungus-farming ant genus Mycetagroicus Brandao Mayhe-Nunes (Hymenoptera, Formicidae, Attini).. 1 records from Myriopoden von Kreta, nebst Bitraegen zur allgemeinen Kenntnis einger Gattungen. 4399 records from Fundacin Miguel Lillo - Coleccin Entomolgica. 204271 records from Essig Museum of Entomology. 17447 records from Swedish Board of Fisheries (Fiskeriverket) - National Register of Survey testfishing. 5 records from LauWi. 10 records from Wiese am Unterbecken. 38 records from Wasserwerkspark (Chemnitz). 15 records from 8c. 82 records from BIRDRACE Die Ziegeneier. 114 records from BIRDRACE VIE will rock you!. 5 records from Faunal assemblage of sediment core GS7603-8. 25230 records from Diveboard - Scuba diving citizen science observations. 125 records from Outer Hebrides Biological Recording Project - OHBRP Otter (Lutra lutra) Dataset - Outer Hebrides. 110506 records from Countryside Council for Wales - Marine data from Countryside Council for Wales (CCW) Technical Support (Research & Monitoring) Contracts, Wales. 52 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/363-1a. 11 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/313-1. 102 records from BIRDRACE HGON Kelkheim-Rumpfteam. 23 records from Plant (JNHM-PL). 339 records from Collection Cnidaria - ZMB. 162 records from Nematode abundance of the Eastern Mediterranean Sea in cold seep sediments collected during the MEDECO2 cruise (2007). 1 records from (Table 4) Plio-Pleistocene benthic foraminifera of ODP Hole 107-652A. 13 records from Florística y biogeografía de algunos bosques mesófilos de la Huasteca Hidalguense: Fase 3 (Chapulhuacán y Pisaflores). 19 records from (Table 5) Ranges of benthic foraminifers from the late Oligocene to the early Miocene in ODP Hole 115-714A. 16 records from Nachtaktiv im Ökogarten (Bad Waldsee). 1138 records from Primera caracterización biológica de hormigas del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 11 records from Meiobenthos investigations in the Black Sea during Poseidon cruise PO317/3. 7161 records from OPAL National Soil Centre, Imperial College London - Earthworm species and associated soil parameters for OPAL National Survey (England only) compiled March 2009 to April 2011. 2 records from Grünanlagen Stadt Brandenburg an der Havel. 1 records from Hausgarten. 15 records from Stadtwald Heide. 20 records from Leben in den Elbwiesen. 456 records from Øvre Heimdalsvatn, Radiocaesium (Cs-137) monitored annually in brown trout (Salmo trutta). 351 records from (Table 2) Abundance of ostracods in surface sediment samples from the Admiralty Bay, King George Island, West Antarctica. 9 records from Benthic macrofauna abundance of sediment core 13200-051. 40 records from Macrofauna abundance in surface sediment sampled during cruise DI237. 753 records from Estación Experimental de Zonas Áridas (CSIC) EEZA-Mamif. 24 records from Echiura - SMF. 248496 records from RSPB - Bird Conservation Targeting Project (BCTP) in the UK, archived data (2001-2008) . 5 records from (Table 7) Relative abundance of benthic foraminifera in ODP Hole 112-683A. 24623 records from Occurrences des observations de la campagne Suivi Aérien de la Mégafaune Marine en France métropolitaine (SAMM1 - Hiver 2011/2012). 691 records from Collection Trilobita SMF. 1522 records from Ibaraki Nature Museum, Fish collection. 24 records from Collection Onychophora - SMF. 5638 records from Estacion Biologica Donana - CSIC, Aves. 3618 records from Fonoteca Zoológica, Museo Nacional de Ciencias Naturales, Madrid: FZ_AMPHIBIA. 9234 records from Davis Strait and Baffin Bay Zooplankton (OBIS Canada). 932 records from BioMar (EurOBIS). 5224 records from Insect Specimens of Omogo Mountain Museum. 2960 records from Herp specimens. 14590 records from Colección de Mamíferos de la Sierra Volcánica Transversal de México (UAM-I). 41646 records from Coleção Entomológica Paulo Nogueira-Neto - IB/USP. 3 records from Total fauna of benthic foraminifera of sediment core Kronsmoor, Late Cretaceous. 22376 records from MfN - Fossil invertebrates Ia. 44 records from Range table from ostracoda in ODP Hole 159-960C. 9 records from (Table 2) Occurrence of benthic foraminifers in ODP Site 116-717. 31 records from Gemeinschaftsaktion Koordinatoren für nachhaltige Bildung/Wittstocker Grundschulen. 12 records from Pollen data of trap CB1. 103 records from Pollen analysis of Site 175-1075 (part 1). 1001 records from Ictiofauna insular del medio y bajo Golfo de California. 3 records from Visual Plants (144.41.33.158) - Herbarium specimen from the Estacion Scientifica San Francisco, Southern Ecuador. 63 records from EURISCO, The European Genetic Resources Search Catalogue. 74 records from Blumenrather Heide / Virneburg. 1 records from Carabodes coriaceus. 65704 records from Coleoptera. 3 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 600 records from Countryside Council for Wales - Bat Roosts Database- South Wales . 51 records from Six new species of ants (Insecta: Hymenoptera: Formicidae) from Egypt.. 146382 records from Swedish Board of Fisheries (Fiskeriverket) - Institute of Coastal Research. 15934 records from Mamíferos de la colección del Instituto Alexander von Humboldt. 5803 records from EcoRecord - Beetle (Coleoptera) Records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 107001 records from Naturalis Biodiversity Center (NL) - Paleontology Invertebrates. 85 records from Birdrace-Die_Paradiesvögel-Herford. 88 records from Birdrace-WeserEggeLäufer-Höxter. 95 records from BIRDRACE BiBi. 1395 records from Alterra (NL) - Microarthropods inventory in grasslands in the province of Friesland. 73 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Anhimidae. 8 records from Benthic macrofauna abundance of sediment core 12930-039. 16276 records from Coleoptera collection of Uunio Saalas. 1 records from Akita Prefectural Museum＋Specimens of Phylum Nemertea of Akita Prefectural Museum. 2 records from Akita Prefectural Museum＋Specimens of Phylum Porifera of Akita Prefectural Museum. 100733 records from South African Institute for Aquatic Biodiversity - Fish Collection (AfrOBIS). 45841 records from Marine and Coastal Management - Linefish Dataset (First Semester of 2004) (AfrOBIS). 8 records from Occurrence of mammalia relicts at site Oberkassel bei Bonn. 746 records from Occurrence of mammalia relicts at site Pestera la Adam. 3 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 1 records from Foraminifera abundance of Hole 21-208. 271203 records from Balfour-Browne Club - Water Beetle Surveys from Britain and Ireland. 11 records from VegetWeb - Repositorium von Vegetationsaufnahmen a. 219492 records from Biodiversity Research and Teaching Collections - TCWC Vertebrates. 83172 records from DMNH Birds. 4 records from Two new species of the genus Chlopsis (Teleostei: Anguilliformes: Chlopsidae) from the Southwestern Pacific.. 10963 records from Nematodes collection (IN) of the Muséum national d'Histoire naturelle (MNHN - Paris). 3587 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Invasive Insecta. 568 records from Coleccion Paleoinvertebrados CCT Mendoza - CONICET. 496 records from Colección Entomológica del Centro Nacional Patagónico “Francisco P. Moreno” (CNP-CE). 8 records from (Table 1) Major and minor element concentrations in the livers of polar bears (Ursus maritimus) from Canada, Alaska and Greenland. 25128 records from rmca-albertine-rift-butterflies. 33144 records from Visdoorgangen - Fish passage places in Flanders, Belgium. 90 records from Birdrace-Uttenreuther_Spatzenzähler-Erlangen/Höchstadt. 54 records from Weidegebiete in der Selzrenaturierung. 10 records from Hertfordshire Biological Records Centre - Hertfordshire Wildlife Site Monitoring Surveys (incomplete). 26 records from Bäche im Mooswald (Vörstetten). 51 records from Naturschutzstation Weinberghaus (Dessau). 2 records from Dinoflagellate cysts of mooring MST-9 (station 915) with cell content. 5 records from Distribution of meiobenthos in sediment core M19_238-2 of the northeastern Atlantic (Table 1). 72 records from Donauinsel des BN bei Entau. 2 records from Bayerische Donau - Neu Ulm. 139 records from Corvids Literature Database. 312 records from Foraminifera and ostracods profile from sediment core AV14_K2-3. 7 records from WA. 5771 records from Macquarie Island Fur Seal Database. 466734 records from ECNASAP - East Coast North America Strategic Assessment (OBIS Canada). 3132 records from Resolute Passage Copepod Distribution (OBIS Canada). 547 records from Invertebrate Collection of Dept. of Ecology. 1587 records from Demersal and pelagic species from the Patagonian shelf (OBIS South America, SOUTHERN OCEAN SUB-NODE). 69009 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1989) (AfrOBIS). 80742 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1996) (AfrOBIS). 321 records from University of New Brunswick Collection. 29477 records from Manitoba Museum of Man and Nature. 21282 records from Coleccion de Herpetologia, MZFC-UNAM. 38736 records from Mammal Collection. 37934 records from South Western Pacific Regional OBIS Data All Sea Bio Subset (South Western P acific OBIS). 2 records from Kochi Prefectural Makino Botanical Garden. 489 records from ANTXXIII-8 Birds and Mammals. 88 records from Gemeindegebiet Weikendorf (Marchfeld). 134 records from National Feral Ferret (Mustela putoris furo) Database. 70 records from Occurrence of mammalia relicts at site Rislisberghöhle. 73 records from Occurrence of mammalia relicts at site Spitzbubenhöhle. 41 records from Occurrence of mammalia relicts at site Sandalja II. 240 records from Occurrence of mammalia relicts at site Roc de Combe. 18 records from Occurrence of mammalia relicts at site Igrita Cave. 19737 records from Colección de Anfibios del Instituto Alexander von Humboldt. 404842 records from Texas A&M University Insect Collection. 140 records from Bunger Hills, 1999/2000 survey - nest sites of snow petrels Pagodroma nivea. 12771 records from Collection Bryozoa SMF. 2 records from Collection Foraminifera SMF. 12819 records from condoncollection. 5 records from Oribatids from Switzerland II. (Acari: Oribatida). (Acarologica Genavensia XC). 104520 records from Monitoring data from the federal state North Rhine-Westphalia (Germany). 2122 records from Fleas (Siphonaptera) of Ireland. 2 records from The ants of El Hierro (Canary Islands).. 1724 records from Fish specimens of Natural History Museum, Kishiwada City. 4 records from Occurrence of mammalia relicts at site Prekonoska Pecina. 11 records from Occurrence of mammalia relicts at site Oelknitz. 26 records from Occurrence of mammalia relicts at site Predmosti. 33 records from Bedfordshire and Luton Biodiversity Recording and Monitoring Centre - Bedfordshire Stylops (BNHS) â 1930-1971. 9 records from Herbarium specimens, Harmas J.H. Fabre (FABR - Sérignan-du-Comtat) of the Muséum national d'Histoire naturelle (MNHN - Paris). 11138 records from Aphidoidea Collection. 4 records from A new species of Eurhabdus from Jamaica (Diptera: Leptogasteridae).. 6 records from Die Milben in der Zoologischen Staatssammlung München. Teil 10. Überfamilie Crotonioidea (I). 120915 records from Marine Biological Association - Marine survey data (Professional) held by MarLIN. . 20810 records from Carabidae of the Carpathians. 2458 records from Colección de Ictiología. 7443 records from Free-living marine Nematodes from San Antonio bay (Río Negro, Argentine).. 410 records from Occurrences des observations de la campagne REMMOA Guyane (2008). 122 records from A second update to the checklist of Finnish long-legged flies (Diptera: Dolichopodidae), with a re-evaluation of the status of Hydrophorus callosoma Frey, 1915. 1 records from On the Australian linyphiid spider Alaxchelicera ordinaria Butler, 1932 (Araneae). 71 records from SysTax - Herbaria. 3 records from A new Costa Rican species of Leptanilloides (Hymenoptera: Formicidae: doryline section: Leptanilloidinae).. 4172 records from USAC Mammals Collection. 41162 records from BioMar - LIFE project. 962 records from Creación de un área protegida pública local en los municipios de Roldanillo, La Unión y Toro.. 113 records from Naturalis Biodiversity Center (NL) - Crustacea. 28 records from Two new species of Pamphobeteus Pocock 1901 (Araneae: Mygalomorphae: Theraphosidae) from Brazil, with a new type of stridulatory organ. 190 records from Inventaire National du Patrimoine Naturel : Observations d'hippocampes et syngnathes de France métropolitaine: Programme Hippo-ATLAS. 26 records from A new species of the Asian schilbid catfish genus Clupisoma from Myanmar, with a redescription of Clupisoma prateri Hora (Osteichthyes: Siluriformes: Schilbidae).. 19127 records from Biological Records Centre - Cerambycidae Dataset. 12 records from (Table 1) Sex, age and numbers of polar bear skulls (Ursus maritimus) collected in Svalbard. 8544 records from The atlas of breeding birds in Małopolska. 51 records from Hertfordshire Biological Records Centre - Hertfordshire Urban Surveys (incomplete). 3 records from New species of the spider genus Olios Walckenaer, 1837 (Araneae: Sparassidae: Sparassinae) from Laos. 381873 records from Royal Dutch Angling Association (SVN) - Piscaria. 3 records from MSB Mammal Observations (Arctos). 1 records from Oribates gilvipes. 14917 records from Vertebrats d'Andorra. 23 records from British Lichen Society - BLS Lichen Database: English churchyards. 10234 records from Collection entomologique Barthélémy. 101 records from Birdrace-Herford-Birder-Herford. 19 records from Artensuche auf den Elbwiesen in Radebeul. 19 records from Erhard Sopp. 10 records from Baumbach Arnsberg, Klasse 12, Fachbereich Biologie. 4 records from Eintauchen in die Natur /Harraser Weg (AWO - Kita Oberheldrungen). 101 records from BIRDRACE nabu-rhein-main.de. 65 records from FFH-Gebiet Paartal. 30 records from Rosarium (LMS), Klasse 6a. 2342 records from Glasaalmigratie - Glass eel migration in the river Yser. 270 records from (Table 2) Fossil record of foraminifera and ostracoda from Muldsberg clay pit, north Germany. 42 records from Collection Aves - PUM. 15 records from Abundance of Elminius modestus in 2007-03 from an experiment in the Wadden Sea off List, Sylt. 117 records from Naturpark Kottenforst-Ville Sammelaktion 15.-19.6.. 16 records from Aktion - Friedensburg Oberschule. 50 records from Rur. 1 records from Kirchenforst. 8345 records from Colección Nacional de Equinodermos Mexicanos (ICMyL-DF, UNAM). 1164 records from Colección de Filópodos del CIBNOR. 29 records from Herbario del CIBNOR. 1325 records from Collection Crustacea ZMG. 42 records from An der Weida zwischen Talsperre Zeulenroda und Vorsperre Weida. 524 records from Fossil (NSMK-FO). 52076 records from Birds (KIEE-BI). 20168 records from Insect (JNHM-IN). 24 records from Admiralty Bay Benthos Diversity Data Base (ABBED). Polychaeta. 1979-80. 394 records from Echinoderms in surface sediments off Sylt collected during Heincke cruise HE255. 12 records from Seawater carbonate chemistry and biological processes during experiments with early life stages of the blue mussel Mytilus edulis, 2010. 1462 records from Biological Records Centre - Dixidae (Diptera) records from Britain and Ireland to 1988. 61888 records from CSIRO Ichthyology provider for OZCAM. 109 records from Triebesbach (Zeulenroda-Triebes). 18 records from Schulgarten der Gesamtschule Am Heidberg. 30 records from Meiofauna abundances in sediments from the Håkon Mosby Mud Volcano (HMMV) obtained during expeditions with Polarstern and Pourquoi Pas ?. 228 records from Cetacean Sightings Survey and Southern Ocean Cetacean Program - BROKE-West. 171 records from Fels- und Weinbergsflächen in Hatzenport/Terrassenmosel. 50 records from Occurrence of mammalia relicts at site Lespezi-Lutarie. 14 records from Occurrence of mammalia relicts at site Stellmoor. 55 records from Occurrence of mammalia relicts at site Pestera Livadita. 4 records from Occurrence of mammalia relicts at site Grotte Cotencher. 44 records from Plantae, TAIF (Taiwan e-Learning and Digital Archives Program, TELDAP). 3 records from Specimens of G. Fenoul Herbarium (FEN). 104 records from Kamptozoa collection of National Museum of Nature and Science. 373 records from Otter survey of Ireland 2004 & 2005. 59016 records from Biological Records Centre - Isopoda (Interim dataset). 46 records from (Appendix) Benthic foraminifera in early Eocene sediments of DSDP Hole 48-401. 1 records from Pelops torulosus. 1 records from Murcia trimaculata. 9 records from Saalewiesen Naumburg. 100 records from Birdrace-ImmerWiederhopf-Lörrach. 102 records from BIRDRACE Westfälische Nachtigallen. 2 records from Wälder und Seen rund um den Mühlenberg. 13 records from (Table 2) Eocene-Oligocene benthic foraminifers abundance in ODP Hole 124-767C. 40 records from Revisión de las categorías en el proyecto de norma oficial mexicana (PROY-NOM-059-2000) para las especies de lagartijas de la familia Anguidae (Reptilia). 168975 records from herpetology. 10760 records from Norbert Kondla Collection. 106 records from Wildes Bremer Leben im Park. 146 records from Occurrence of mammalia relicts at site Laugerie-Haut e-Est. 57 records from Occurrence of mammalia relicts at site Teufelsbrücke. 16 records from (Table V) Distribution of diatoms in samples from Heidemann Valley trench, Antarctica. 860885 records from South Australia Fauna Observations. 16 records from Herbarium of the Université Libre de Bruxelles. 37 records from Roter Berg Werdau (Leubnitz). 26 records from Bolzplatz. 20 records from The interstitial subsoil fauna of the medium beach level at Sarso Beach, Red Sea (Table 3). 3 records from Distribution of meiobenthos in sediment core M19_216-2 (2) of the northeastern Atlantic (Table 1). 28 records from Schriesheimer Steinbruch. 25 records from Laubmischwald bei der Internationalen Grundschule Potsdam. 40 records from Raus in die Natur. 44 records from Range table from ostracoda in ODP Hole 151-910D. 71 records from (Table 2) Quarternary ostracod abundance in sediment core CRP-1. 95 records from Late Cretaceous and Cainozoic bathyal Ostracoda of DSDP Site 62-463 in the Central Pacific (Fig. 3). 103 records from Mammals (UWEP-MM). 225 records from Echinoderms in surface sediments off Sylt collected during Heincke cruise HE262. 4 records from (Appendix B) Calcareous benthic foraminifers in ODP Hole 123-765C. 8525 records from Literary descriptions of Iranian lizards. 34 records from sediments composition of surface sediment samples Men4377-7 to Men4418-1. 1 records from Palynological investigation of surface sample of profile Tso Kar. 1700 records from Nuevos registros de esponjas del Pacífico mexicano, Mar de Cortés y Archipiélago Revillagigedo. 569 records from Insectos del orden Trichoptera de la Sierra Tarahumara, Chihuahua, México. 1134 records from Ictiofauna de los corredores biológicos Sierra Madre del Sur y Selva Maya Zoque. 5 records from Benthic macrofauna abundance of sediment core 12930-059. 1547 records from Alterra (NL) - Entomofauna inventory in Speulder forest. 11333 records from Colección de referencia de vectores de Leishmania spp (causante de Leshmaniasis cutánea localizada) de la Península de Yucatán y un estudio preliminar en un área endémica de Quintana Roo. UADY_SNIB. 84270 records from Actualización y enriquecimiento de las bases de datos del proyecto de evaluación y análisis geográfico de la diversidad faunística de Chiapas. 461 records from Distribución de peces dulceacuícolas introducidos en las cuencas del México central, con especial atención a las localidades dentro del área de distribución de los peces endémicos de la familia Goodeidae. 142 records from Endocast Collection -CONICET- Argentina. 60445 records from Bureau of Rural Sciences National commercial fisheries half-degree data set 2000-2002 (OBIS Australia). 1492 records from Cetacean distribution in the South Atlantic and South Pacific Ocean (AR-OBIS) (OBIS South America, SOUTHERN OCEAN SUB-NODE). 6 records from Pollichia Pilzherbar. 35 records from The ant genus Tetraponera in the Afrotropical region: the T. grandidieri group (Hymenoptera: Formicidae).. 1 records from Die vom k. k. Oberartze Herrn Dr. Justyn Karlinski im Jahre 1887 in Bosnien, der Herzegowina und in Novibazar gesammelten Myriopoden. 2 records from Abundance of benthos infauna at station PS1241-1. 4290 records from Registros biológicos de especies de fauna vertebrada terrestre en las centrales de San Carlos y Jaguas - 2009. 859 records from Royal Horticultural Society - RHS berberis sawfly (Arge berberidis) monitoring . 3201 records from Weevils of the Carpathians. 1 records from Neue Milbenarten aus Kärnten. 66 records from Feriendorf Ober-Seemen. 120 records from Birdrace-The_early-Birds-Minden/Lübbecke. 81 records from Birdrace-Die_Ornithomaten-Herford. 157 records from BIRDRACE Rheinische Wasserrallen. 102 records from http://www.geo-artenvielfalt.de (www.geo-artenvielfalt.de) - BIRDRACE *Akassine*. 106 records from BIRDRACE EFTAS-NLU Birdrace Team 2008. 18 records from Mönchspark. 9067 records from Atlas Nacional de Anélidos Poliquetos de México (ICMyL-DF, UNAM). 1368 records from EDIT - ATBI in Spreewald (Germany). 6806 records from Collection Collembola - SMNG. 8789 records from MfN - Mallophaga Collection. 175 records from Unionids data from National Water Research Institute. 5774 records from Coleoptera of Białowieża Forest. 430 records from Erlengraben/Lipp-Tal (Östringen). 6 records from Moema apurinan sp. n. and Aphyolebias boticarioi sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): two new annual killifishes from the Rio Purus basin, Brazilian Amazon.. 2 records from Occurrence of mammalia relicts at site Dechenhöhle. 48 records from A new species of Psilorhynchus (Teleostei: Psilorhynchidae) from the Ataran River Basin, Myanmar, with comments on the generic name Psilorhynchoides.. 33560 records from Butterflies of Ireland. 1 records from Dorset Environmental Records Centre - Bryophyte Survey of the Poole Basin Mires - NBN South West Pilot Project Case Studies. 1665 records from Field Study Group of the Dutch Mammal Society (NL) - 2005 - Mammal Survey Pol'ana Biosphere reserve, Slovakia. 77 records from Terrestrial gastropods of Srebarna Nature Reserve, North-Eastern Bulgaria (Gastropoda). 3065 records from Colección de Ofidios Museo de La Salle Bogotá (MLS). 2 records from (Supplement 3) Dinoflagellate cyst concentrations of the three transects OMZ (GeoB 12312, 12321, 12331), below-OMZ-seep (GeoB 12326), and OMZ-seep (GeoB 12328). 118 records from Birdrace-Blind_vor_Birds_BVB_Kranenburg07-Kleve. 11 records from VFD-H: Rheingau: Pferdeweide Loock. 68 records from Coleoptera identified from the Bellot Street site, Greenwich, London. 159 records from Relative abundance of ostracods in sediment core St09. 17 records from Mites of the genus Malaconothrus (Acari: Cryptostigmata) from the British Isles. 25425 records from Birds (JNHM-BI). 9 records from Recuento de la diversidad florística de Veracruz. 5549 records from National Survey on Odonata. 1224 records from Provincial Museum of Alberta. 138 records from Danish Mycological Society, fungal records database. 3654 records from Antarctic Euphausiacea occurence data from "German Antarctic Marine Living Resources" (GAMLR) Expeditions. 121 records from Table II: Birds observed at the Weddell Sea during the period: 22 December 1959 to 14 January 1960. 381 records from Estudio taxonómico de moluscos terrestres y dulceacuícolas de la región maya de México I. Reserva de la Biosfera Pantanos de Centla. 45 records from Crustacea specimens of Kuroshio Biological Research Foundation. 45 records from (Table 1) Distribution of early late Eocene fossil content in ODP Hole 115-715A. 50 records from West-, Central- and East African Plants Databases. 153869 records from Seabirds of the Southern and South Indian Ocean. 113941 records from Pacific Ocean Shelf Tracking (OBIS Canada). 42504 records from Fish specimens of Fisheries Research Laboratory Mie University. 144953 records from Vertebrate Zoology Division - Ornithology, Yale Peabody Museum. 2 records from (Supplement 3) Dinoflagellate cyst count data by species of the three transects OMZ (GeoB 12312, 12321, 12331), below-OMZ-seep (GeoB 12326), and OMZ-seep (GeoB 12328). 495 records from Life Science National Tsing Hua University. 7317 records from NCOS (OBIS China). 6348 records from South Western Pacific Regional OBIS Data Bryozoan Subset (South Western Paci fic OBIS). 23 records from Schulgelände IGS Kaufungen. 28 records from Artenbestimmung. 1477 records from Artenvielfalt auf der Weide - GEO-Hauptveranstaltung in Crawinkel. 131 records from Occurrence of mammalia relicts at site Veternica. 9 records from Occurrence of mammalia relicts at site Adler Cave xx. 3 records from Occurrence of mammalia relicts at site Sesselfelsgrotte. 15 records from Occurrence of mammalia relicts at site Icoana. 12 records from New data on the European species of three genera Scelionidae (Hymenoptera).. 785 records from Colección Osteológica de Mamíferos Marinos del CENPAT. 794 records from Walter Herwig 1978 (FFS): SeaStars (Echinodermata, Asteroidea). 5056 records from Nest census, Windmill Islands 2002/03. 43891 records from Collection Mollusca SMF. 18518 records from University of British Columbia - Spencer Entomological Collection (UBCZ). 316 records from Hymenoptera, NEF. 18403 records from Oregon State Ichthyology Collection. 333 records from Revisión del género Zabrotes para México (Coleoptera: Bruchidae). 6 records from Flora del Valle de Tehuacán-Cuicatlán: II Fase. 786 records from Universidad Industrial de Santander, Museo de Historia Natural, Colección de Mastozoología. 33728 records from AIMS - Baited Remote Underwater Video Station (OBIS Australia). 3420 records from Nova Scotia Museum of Natural History, Halifax, NS, Canada. 101 records from CNAN/Escorpiones Estado de Mexico. 74817 records from Bird and Mammal specimens. 556 records from RMT Trawl catch from 1985/86 V1 ADBEX III voyage. 9195 records from Shellfish Specimens of Miyazaki Prefecture Museum of Nature and History. 15414 records from Staffordshire Ecological Record - SER Site-based Surveys. 4455 records from University of Alberta Museums, Amphibian and Reptile Collection. 133 records from Faberpark (Nürnberg/Stein). 39 records from Friedhof Friedenstraße (Berlin). 102 records from Halberg bei Neumorschen. 92 records from Birdrace_TerraCamper-Münster. 31 records from Occurrence of mammalia relicts at site Cueva Millan. 10 records from Occurrence of mammalia relicts at site Nazeing. 414336 records from Biological and palaeontological collection and observation data MNHNL. 12 records from Botany Division, Yale Peabody Museum. 2 records from Collection Paläobotanik SMB. 1 records from Abundance of benthos infauna at station GIK23040-1. 1 records from Abundance of benthos infauna at station GIK23065-1. 84986 records from NINA Vanndata fisk. 70 records from Revisions of Australian ground-hunting spiders. V. A new lycosoid genus from eastern Australia (Araneae: Tengellidae). 30428 records from Birds collection (ZO) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 18 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Especies observadas en Mercedes (Unterkofler, octubre 1999). 18354 records from Hokkaido University Coleoptera Collection. 433 records from A taxonomic revision of the Formica rufibarbis Fabricius, 1793 group (Hymenoptera: Formicidae).. 5148 records from Colección de Reptiles - Museo de Herpetología de la Universidad de Antioquia. 2 records from Myrmica afghanica (Hymenoptera: Formicidae), a new ant species from Afghanistan.. 1200 records from Insect specimens of Natural Museum of Geihoku. 52 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Especies observadas en Casilda (Luna & Piazza, octubre 1999). 23 records from New species of the plesiomorphic genus Nixonia Masner (Hymenoptera: Platygastroidea, Platygastridae) from South Africa.. 1 records from Carabodes cephalotes. 5 records from Countryside Council for Wales - Sightings & Miscellaneous Data from Countryside Council for Wales (CCW), 2008 onwards. 269 records from Succession of benthic hard-bottom communities abundance at station Errina2012_IS_solar2. 5733 records from Small Mammal Research Database. 352 records from Scottish Natural Heritage - Recovery of the medicinal leech Hirudo medicinalis in Scotland - Phase II. 6507 records from Likona Invertebrates. 48 records from (Fig. 2) Vertical density profiles of meiofauna taxa in surface sediments of Potter Cove, King George Island, Antarctic Peninsula. 2 records from Ituglanis paraguassuensis sp. n. (Teleostei: Siluriformes: Trichomycteridae): a new catfish from the rio Paraguacu, northeastern Brazil.. 1806238 records from Dutch Foundation for Applied Water Research (STOWA) - Limnodata Neerlandica. 128 records from Plants galls. 1 records from Die Myriopodenfauna von Albanien und Jugoslavien. 6 records from Description of two new species of the catfish genus Trichomycterus from southeastern Brazil (Siluriformes: Trichomycteridae).. 2 records from UAM Herbarium (ALA), Vascular Plant Collection (Arctos). 46 records from Waldstück Bremerhagen LK Bio Kl. 12. 53 records from Bad Bodenteicher Heide. 16006 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Peces Continentales. 30 records from Distribution of meiofauna in surface sediments of the Iberian deep sea basin (Table 3). 2 records from Distribution of meiobenthos in sediment core M19_234-2 of the northeastern Atlantic (Table 1). 7 records from Meiofauna abundance in sediment core 13368-015. 17 records from Megafauna abundance and biomass from trawl samples obtained during cruise DI229. 51 records from Matter enrichment of the macrofauna community of MAC station 13077-001. 6 records from Benthic macrofauna abundance of sediment core 12930-084. 505 records from Avifauna de la Isla de Cozumel, Quintana Roo_2. 1 records from Pollen analysis of sediment profile NMS0 from Neumühler See. 26882 records from KUBI Ornithology Tissue Collection. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 292 records from Gymnotus ucamara: a new species of Neotropical electric fish from the Peruvian Amazon (Ostariophysi: Gymnotidae), with notes on ecology and electric organ discharges.. 9216 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Diptera_Tipulidae_NL. 1061 records from Abundance of megabenthic species in trawl catches per station in addition to table 2 during POLARSTERN cruise ARK-VIII/2 (EPOS). 2798 records from Merseyside BioBank - North Merseyside Fish (unverified). 1 records from (Table 1) Concentration of PCB and other contaminants in blood plasma of polar bears (Ursus maritimus) from Svalbard. 27 records from Haarbach Höfe. 121 records from BIRDRACE Die Schwenker-Birder. 150 records from Redescription and generic placement of the spider Cryptachaea gigantipes (Keyserling, 1890) (Araneae: Theridiidae) and notes on related synanthropic species in Australasia. 86 records from Distribution of the sand-ascidian Seriocarpa rhizoides in surface sediments of Josephine-Bank, North Atlantic (Table 4). 25 records from Pollen profile form Hickory Ridge Basin, Illinois, U.S.A. 20 records from Lebensraum Walram. 72 records from Feuerlöschteich, Wald und Dünen in den Holmer Sandbergen. 38 records from Bonner Schülerinnen am Rodder Maar. 2515 records from Baillon Collection. 28 records from Ostracoda abundance of Hole 48-405. 24 records from Range table from ostracoda in ODP Hole 151-911A. 11 records from Benthic macrofauna abundance of sediment core 13200-077. 57 records from Macrofauna abundance in surface sediment sampled during cruise DI231. 746 records from RMT Trawl catch from the 1986/87 V7 AAMBER voyage. 9 records from Molluscs in surface sediments off Sylt collected during Heincke cruise HE233. 6 records from Benthic macrofauna abundance of sediment core 13200-008. 64 records from Landings of European lobster (Homarus gammarus) and edible crab (Cancer pagurus) in 2006, Helgoland, North Sea. 82 records from Admiralty Bay Benthos Diversity Data Base (ABBED). Cumacea.. 18 records from Crustacea in surface sediments off Sylt collected during Heincke cruise HE218. 2501 records from Helmintos parásitos de peces del sureste de México. 6 records from Estudio de la diversidad florística en la región de la Chinantla, Sierra Norte de Oaxaca. 35 records from Akita Prefectural Museum＋Reptiles Specimens of Akita Prefectural Museum. 88302 records from Instituto de Investigación CIBIO, Universidad de Alicante: CEUA. 2883 records from Inventory of Antarctic seabird breeding sites. 41 records from Occurrence of mammalia relicts at site Sveduv stul. 129 records from Squid specimens from the 1991/92 V6 AAMBER2 voyage. 1 records from Ulteriore contributo alla conoscenza dei chilopodi di Grecia. 1 records from Hoplophora longula. 45308 records from Biological Records Centre - Water Bug (aquatic Heteroptera) data for Britain . 8195 records from Colección de anfibios - Museo de Herpetología de la Universidad de Antioquia. 27205 records from UAM Entomology Observations (Arctos). 67 records from Bioimages. 6 records from University of Amsterdam (NL) - Páramo vegetation research, Venezuela.. 8007 records from Segunda caracterización biológica de aves del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 19 records from The first case of aggressive mimicry among lamprologines in a new species of Lepidiolamprologus (Perciformes: Cichlidae) from Lake Tanganyika.. 4653 records from Colección Limnológica Universidad de Antioquia. 68 records from RSPB - Bean geese on the Slamannan Plateau, Central Scotland between 1993 and 1995 (RSPB/SNH/Bean Geese Action Group). 71 records from Steinbruch Mainz-Weisenau. 11 records from Waldwiese. 25 records from Schulhofuntersuchung Thomas-Mann-OS. 296 records from Echinoderms in surface sediments off Sylt collected during Heincke cruise HE233. 465 records from Macrobenthos in surface sediments off Sylt collected during Heincke cruise HE293. 45 records from Crustacea in surface sediments off Sylt collected during Heincke cruise HE258. 1 records from Murcia rubra. 168716 records from National Butterfly Survey of Finland. 2 records from Herbarium, Centre for Biodiversity, University of Turku, Finland (TUR). 26721 records from Bird Observational Records. 557 records from Cross Sands broadscale survey 1998 (EurOBIS). 58614 records from Marine and Coastal Management - Demersal Surveys (years 1986-1990) (AfrOBIS). 61010 records from Fish Collection of Hokkaido University. 64839 records from Mammals Specimens. 5346 records from Araneidae specimen database of Osaka Museum of Natural History. 9633 records from Coleção Entomológica do Depto. de Sistemática e Ecologia. 293 records from Gewann Krampf (Heilbronn). 33 records from Schulumfeld Albert-Einstein-Gymnasium (Sankt Augustin). 48 records from VSN-Wiese. 16 records from Occurrence of mammalia relicts at site le Roc de Marcamps. 5 records from Occurrence of mammalia relicts at site Barova Cave. 11 records from Occurrence of mammalia relicts at site Klithi. 5 records from Foraminifera abundance of Hole 39-357. 1 records from Arthropoden aus südostalpinen Höhlen.. 45066 records from Colección Nacional de Herpetología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 318 records from Gunma Museum of Natural History, Amphibia and Reptile Specimen. 32214 records from Collection Aves (spirit preserved) SMF. 8 records from Abundance of epibenthic echinoderms at seafloor photography station PO196_1024. 4 records from Faun. 10 records from Description of the larval stages of the Shield Darter, Percina peltata (Pisces: Percidae), in New York.. 631 records from RSPB - 2008 Twite (Carduelis flavirostris) Breeding Season Survey, Wales RSPB/CCW. 20 records from Threatened Species programme. 28767 records from Animal Sound Archive. 2 records from Neobythitoides serratus, a new bathyal genus and species from the East China Sea (Teleostei, Ophidiidae).. 6943 records from DMNS Egg Collection (Arctos). 65 records from A new species of Rineloricaria (Siluriformes: Loricariidae) from the Paraná and Uruguay River basins, Misiones, Argentina.. 44 records from Colección osteológica de mastozoología marina. 1 records from Vascular Plant Collection - University of Washington Herbarium (WTU). 73821 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1986) (AfrOBIS). 40812 records from Marine and Coastal Management - Linefish Dataset (First Semester of 2005) (AfrOBIS). 30302 records from Arizona State University Amphibian and Reptile Collection. 12 records from Arizona State University Lichen Collection. 22 records from Meiofauna abundances in sediments from the Nyegga pockmark area (Norwegian Sea) obtained during the VICKING expedition in 2006. 1 records from ATCC Bacteria Collection Catalog. 9 records from Impetus - Herbarium Hamburgense. 41271 records from KUBI Ichthyology Collection. 3 records from Benthic foraminifera abundance of Hole 34-320. 1017 records from Broadland Environmental Services Limited - Water vole distribution within Broadland (2003-2006): based upon field signs, sightings and trapping data.. 3311 records from Craneflies of Ireland. 10 records from Oberservation of birds at station PS14/158 along 49° West. 56 records from Polychaeta abundance in surface sediments of the east Greenland continental slope (79° N section). 20570 records from Colección Nacional de Ornitología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 31 records from Descriptions of a new species and previously unknown males of Nesticus (Araneae: Nesticidae) from caves in Eastern North America, with comments on species rarity. 1985 records from Seabird 2000. 7768 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Platyhelminthes. 2 records from On the female of Gypona reversa DeLong & Martinson, 1972, with emphasis on genital structures (Insecta: Hemiptera: Cicadellidae). 66 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Especies observadas en el Parque Provincial Salto Encantado (Guller et al.a, marzo 1997). 211 records from Collection Mammalogie - ZSRO. 49361 records from Nottinghamshire Biological and Geological Records Centre - UK abstract from Nottingham City Museums & Galleries (NCMG) Insect Collection Baseline database. 19 records from Two sympatric species of Antrodiaetus from southwestern North Carolina (Araneae, Mygalomorphae, Antrodiaetidae). 83 records from Eden Rivers Trust - White-clawed crayfish (Austropotamobius pallipes) distributions within four sub-catchments of the River Eden Catchment, Cumbria 2007-2008 . 71 records from KARSTLANDSCHAFT SÜDHARZ - VOM GIPSABBAU BEDROHT (Grenzstreifen am Röseberg). 2 records from Range table from benthic foraminifers in ODP Hole 192-1183A. 4 records from First description of the female of the spider Savignia zero Eskov, 1988 (Araneae: Linyphiidae). 62 records from National Inventory of Swiss bryophytes. 15 records from Pollen analysis of sediment profile MU1 from Muggesfelder See. 95840 records from UTEP Vertebrates. 1 records from Miriapodi di alcune grotte della Campania. 7566 records from National Barkfly Recording Scheme - Outdoor Psocoptera (barkfly) records for Britain & Ireland, 1850 to present.. 75791 records from SAIAB. 75 records from New species of the Eastern Hemisphere genera Afroheriades and Noteriades (Hymenoptera, Megachilidae). 28 records from Herbarium specimens of Association des Naturalistes de la vallée du Loing (ANVL). 13 records from Regenwasserabfangsbecken (Erlenbach). 112 records from BIRDRACE Gütersloher Gimpel. 4 records from Distribution of meiobenthos in sediment core M23_199 of the northeastern Atlantic (Table 1). 75 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/356-1. 2 records from Ökosysteme rund um Wedel. 327617 records from Herps. 532 records from (Appendix 2) DSDP Site 94-610 ostracode species census data. 3 records from Pollen record of profile 3TZ2. 3 records from Pollen analysis of surface samples near sediment core Fiekers Busch. 43356 records from Canadian Museum of Nature Fish Collection. 892 records from (UTC) University of Tennessee Mammals Collection. 156 records from Colecciones Zoológicas de la Universidad de León, Colección de Malacostráceos. 16 records from Lichen Collection - University of Washington Herbarium (WTU). 1 records from Herbarium specimens of Bamboo collection Prafrance Générargue (BAMBO). 5 records from Pollen profile RAC20, Lake Racou, France. 1627 records from The Irish Squirrel Survey 2007. 20891 records from Biological Records Centre - Brachycera (Diptera) records from Britain and Ireland to 1990. 57 records from New records of ants (Hymenoptera: Formicidae) from Iran.. 41 records from Scottish Natural Heritage - Site Condition Monitoring of Annex II Vertigo species in Scotland. 4447 records from Lepidoptera (Observations). 2 records from On the centipedes (Chilopoda) of the Republic of Macedonia. 39 records from Landschaftsschutzgebiet Buchhorst 4. 128 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña enero 2007. 14 records from Megafauna abundance and biomass from trawl samples obtained during cruise DI237. 4 records from (Table 4) Occurrence of benthic foraminifers in ODP Hole 116-719A. 5 records from Penguins of Antarctica. 108 records from Antarctic Amphipoda. 195 records from Aportación al conocimiento de la fauna de Ascidias del litoral Pacífico de México. 4357 records from Lothian Wildlife Information Centre - Lothian Wildlife Information Centre Secret Garden Survey. 1381 records from Actualización de la base de datos de la colección mastozoológica de El Colegio de la Frontera Sur, San Cristóbal de las Casas. 1200 records from Invertebrate specimens of Toyama Science Museum. 1 records from Universität Salzburg. 286001 records from Edaphobase. 93840 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1989) (AfrOBIS). 47502 records from Fish specimen database of Osaka Museum of Natural History. 21593 records from CNCR/Colección Nacional de Crustaceos. 274 records from Detection histories for eight species of Amazona parrots in Venezuela during the NeoMaps bird surveys in 2010. 191 records from Chinese species of egg-parasitoids of the genera Oxyscelio Kieffer, Heptascelio Kieffer and Platyscelio Kieffer (Hymenoptera: Platygastridae s. l., Scelioninae). 4 records from Pollen analysis of sediment profile HAE10 from Haemelsee. 87134 records from Sheffield Bird Study Group - Sheffield Bird Study Group (Yorkshire records). 2546 records from The atlas of butterflies in Kraków. 96 records from Trichoptera (caddisflies) of Ireland. 1 records from On the Chilopoda from Turkey. 634 records from EcoRecord - Fish records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 813 records from Cambridgeshire & Peterborough Environmental Records Centre - Chippenham Fen Moth surveillance project. 22 records from Königsdorfer Wald. 8 records from Benthic macrofauna abundance of sediment core 13077-070. 313 records from Colecciones Zoológicas de la Universidad de León, Colección de Insectos. 35 records from Ortsrand Zandershagen. 304 records from Antarctic Marine Species Sequence Data. 200 records from Macrobenthos in surface sediments off Sylt collected during Heincke cruise HE233. 23 records from Benthic and planktonic foraminifera in ODP Hole 123-766A (Table 1-4). 72 records from (Table 8) Distribution of ostracode species in surface sediments of the eastern Laptev Sea. 246 records from Repatriación del material ictiológico de 12 estados de la República Mexicana, depositado en la colección ictiológica de la Universidad de Tulane, E.U.. 5323 records from Anfibios y reptiles del estado de Nuevo León. 327 records from Elaboración de las fichas técnicas para la evaluación del riesgo de extinción de 18 especies de peces dulceacuícolas mexicanos. 2025 records from Los crisomélidos del bosque mesófilo de la reserva de la biósfera El Cielo, Gómez Farías, Tamaulipas. 84 records from E.C. Manning Park Collection. 3 records from Guadeloupe_Herbier. 510 records from (Tab. 9.D) Presence and abundance of benthic fauna at station FINO 1 in 2005. 794 records from National Trust for Scotland - NTS Properties Sensitive Species Records 1800-2013. 117 records from BTCV Scotland - BTCV wildlife counts recording workshops. 598 records from Scorpiones collection (RS) of the Muséum national d'Histoire naturelle (MNHN - Paris). 81388 records from natagora-earlybirds. 3942 records from TTRS Ornithology. 808 records from Greater Manchester Ecology Unit - Distribution of Great Crested Newts in Greater Manchester. 30 records from (Appendix) Foraminifer abundance of a volcaniclastic interval from ODP Hole 197-1206A. 26 records from Schwedische Oribatei (Acari). III.. 1 records from Zetes morticinus. 26 records from Kabelskebach (Kabelsketal, Saalkreis). 35 records from Alter Kreidebruch Saßnitz/Rügen. 3 records from Mainfränkischer Trockenrasen und Naturschutzgebiet Höhfeldplatte bei Veitshöchheim. 4472 records from MVZ Bird Observations (Arctos). 7 records from Schulhof A.-Schweitzer Schule (Wetzlar). 102 records from BIRDRACE Willi goes Birding. 48 records from Schulgarten Janusz-Korczak-Realschule. 15896 records from Scottish Environment Protection Agency - Scottish river macro-invertebrate records from 2007 collected by SEPA. 1775 records from Benthos counted on dredged samples during Valdivia cruise VA44. 29 records from Oberes Schindelbachtal. 7 records from Ostracoda abundance of Hole 24-238. 8 records from Range table from ostracoda in ODP Hole 143-865A. 8 records from Meiofauna abundance in sediment core 12930-015. 33 records from The Fungal Collection at the Senckenberg Museum für Naturkunde Görlitz. 1240 records from Sponge collection of National Museum of Nature and Science. 181 records from Análisis del ictioplancton del ecosistema costero de Celestún, Yucatán. 3 records from Herbario UNAP. 17334 records from Museo Nacional de Ciencias Naturales, Entomología. 755472 records from Inventaire National du Patrimoine Naturel : Oiseaux hivernants de France. 63 records from Fonoteca Zoológica, Museo Nacional de Ciencias Naturales, Madrid: FZ_INSECTA. 47 records from Petrography, carbonate mineralogy and texture of carbonate rocks of Meteor and Josephine Seamounts, eastern North Atlantic (Table 5). 2107 records from Collection Polychaeta - ZSRO. 4 records from (Table 7) Relative abundance of benthic foraminifera in ODP Hole 112-683B. 38 records from (Table 17) Distribution of ostracode species in Core PS51/092-12. 70 records from Catch related distribution of Appendicularia at station M9_A near the Great Meteor Bank, Northeast Atlantic (Table 7). 3702 records from Vertebrados terrestres del parque nacional Cañón del Sumidero, Chiapas, México. 3524 records from Escarabajos y moscas de los bosques de niebla del sureste mexicano (Coleoptera: Scarabaeoidea; Diptera: Syrphidae y Calliphoridae). 43242 records from Bentos collection of the Museum of Nature and Human Activities, Hyogo. 877161 records from Finnish Winter Bird Census. 243 records from Memorial University Department of Biology Collection. 6323 records from Canadian National Collection of Insects. 1070 records from CNAN/Araneae. 2174 records from Den store sneglejagt ("The great snail-hunt"). 592 records from Antarctic Krill occurrence data from Ukraine YUGNIRO Institute. 83 records from Am Moosangerweg. 1 records from Abundance of benthos infauna at station GIK23055-1. 23 records from Benthic meiofauna abundance in surface sediment during cruise CD86. 29 records from Abundance of epibenthic echinoderms at seafloor photography station PO196_1009. 2109 records from Harvestmen (Opiliones) of Ireland. 78 records from The Deepwater Program: Northern Gulf of Mexico Continental Slope Habitat and Benthic Ecology - DgoMB: Polychaetes. 128 records from Distribution of microorganisms in recent sediments of Kiel Bay. 1388 records from Birds - Wild Birds (KIDR-BI). 3483 records from Arthropod fauna in christmas tree plantations. 16425 records from Coleção Entomológica Pe. Jesus Santiago Moure (Hymenoptera). 1 records from Arthropoden aus südostalpinen Höhlen.. 42 records from Hüttenseepark (Meißendorf). 36 records from Landschaftsschutzgebiet Hexenberg (Erftstadt-Erp). 155 records from Birdrace-Gätkes_Erben-Lüneburg. 25 records from Occurrence of mammalia relicts at site Tokod-Nagyberek. 1 records from Nothrus theleproctus. 131 records from Abundance of birds in the Lena Delta Region. 16469 records from Arbeitsgemeinschaft Heuschrecken Österreichs. 745 records from Gunma Museum of Natural History, Mammal Specimen. 61 records from A taxonomic revision of the catshark genus Holohalaelurus Fowler 1934 (Chondrichthyes: Carcharhiniformes: Scyliorhinidae), with descriptions of two new species.. 54 records from Outer Hebrides Biological Recording Project - OHBRP Vertebrates (except birds and restricted records) Dataset - Outer Hebrides. 1 records from Hoplophora straminea. 19356 records from Hymenoptera. 3570 records from Taiwan Fisheries Research Institute – Digital archives of coastal and offshore specimens. 17 records from MVZ Herp Observations (Arctos). 27988 records from Argyll Bird Club - Bird records for Argyll for the years 2002 and 2003. 6 records from Relationships of the New World cichlid genus Hypsophrys Agassiz 1859 (Teleostei: Cichlidae), with diagnoses for the genus and its species.. 19 records from Banc de dades de biodiversitat de Catalunya-FungaCat. 47 records from GEO-Tag der Artenvielfalt auf dem Bausenberg mit den 4. Klassen der Brohltaler Grundschulen. 6 records from Type specimen data for Nicrophorus efferens Sikes & Mousseau. 9 records from Oberservation of birds at station PS14/145 along 49° West. 27945 records from EDIT - ATBI in Mercantour/Alpi Marittime (France/Italy). 21 records from RSPB - Twite, winter distribution in Caithness and Sutherland 2006/7. 23 records from Benthic macrofauna abundance in surface sediments of the east Greenland continental slope (79° N section). 2 records from Pollen analysis of sediment profile KR0 from Kreutzsee. 1 records from Chilopoden und Diplopoden aus Jugoslavischen Höhlen. 300 records from A systematic revision of the genus Archocentrus (Perciformes: Cichlidae), with the description of two new genera and six new species.. 2 records from Gymnotus ardilai: a new species of Neotropical electric fish (Ostariophysi: Gymnotidae) from the Rio Magdalena Basin of Colombia.. 214962 records from Sheffield Biological Records Centre - Sheffield Biological Records Centre- Non-sensitive Records from all taxonomic groups. . 1 records from Nothrus posticus. 5277 records from FloVegSI-FAV - Faunistical database of ZRC SAZU. 2 records from Occurrence of mammalia relicts at site Grotte du Bichon. 114 records from Occurrence of mammalia relicts at site Gare de Couze-Serie 2. 13247 records from Distribution Atlas of Butterflies in Ireland 1979 (An Foras Forbartha). 92982 records from Butterflies - Irish Butterfly Monitoring Scheme. 15131 records from ARC Bees. 6328 records from Naturalis National Natural History Museum (NL) – Indo-Pacific Plio-Pleistocene fossils. 5262 records from Spider Mites Collection of Jean Gutierrez. 1 records from Murcia acaroides. 8851 records from RSPB - Odonata records from RSPB Reserves 1970-2009 (RSPB). 814 records from Biological Records Centre - Orthoptera and Allied Insects of the British Isles data from iRecord . 191 records from Chinese species of egg-parasitoids of the genera Oxyscelio Kieffer, Heptascelio Kieffer and Platyscelio Kieffer (Hymenoptera: Platygastridae s.l., Scelioninae). 3270 records from The Pisces Collection at the Staatssammlung für Anthropologie und Paläoanatomie München. 1957 records from Record, the Biodiversity Information System for Cheshire, Halton, Warrington and the Wirral - RECORD unverified freshwater fish data up to current day. 3 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 6 records from Collection Myriapoda - SNSD. 683 records from Thames Valley Environmental Records Centre - Natural England Bat Records for Berkshire and Oxfordshire (Held by Thames Valley Environmental Records Centre). 7 records from University of Amsterdam (NL) - Páramo vegetation research, Talamanca Cordillera, Costa Rica. 67 records from Birdrace-Guckers_Offenbach-Offenbach. 108 records from BIRDRACE Diesmal sehen wir mehr. 30 records from Occurrence of mammalia relicts at site Trebacki krs. 22 records from Akrokolioplax, a new genus of Southeast Asian labeonine fishes (Teleostei: Cyprinidae).. 1 records from (Tab. 7) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 43-384, J-Anomaly Ridge, Grand Banks off Nefoundland. 133 records from Kohlstattbrunnental. 2377 records from Dutch Mammal Society (NL) - Mouse observations of life trap studies extracted from historic reports. 1 records from Chilopoden und Diplopoden aus Jugoslavischen Hoehlen. 39 records from Lebensraum Fluß/Zwickauer Mulde in Wolkenburg. 58 records from Naturschutzgebiet Kochertgraben. 14 records from Lustbach-Umland. 1770 records from Schmidt Museum of Natural History_Birds. 49 records from Heavy metals in abdominal parts of Pagurus bernhardus during VALDIVIA cruise VA44. 6659 records from Anfibios y Reptiles del Estado de Tamaulipas, México (UANL). 30 records from Akita Prefectural Museum＋Amphibians Specimens of Akita Prefectural Museum. 4 records from (Table 2) Abundance of the main species in the assemblage Elphidium clavatum-Cassidulina reniforme of the Kara Sea. 127499 records from Southern Ocean Continuous Zooplankton Recorder (SO-CPR) Survey. 1110 records from Folklore and Natural History Museum Insect. 48 records from Gwaii Haanas Marine Plants (OBIS Canada). 1263 records from Benthic fauna in the Pechora Sea (EurOBIS). 29 records from Osservazioni sui Chilopodi dell'Appennino lucano e calabrese (Chilopoda). 1069 records from ZFMK Sound Archive. 5 records from (Table 1) Distribution of Cretaceous redeposited benthic foraminifers at DSDP Hole 89-585. 2 records from A new species of the genus Xysticus C. L. Koch from Turkey (Araneae: Thomisidae). 968 records from TTRS Mammals. 69982 records from Lepidoptera collection, Natural History Museum, University of Oslo. 24853 records from Georgia Southern University - Savannah Science Museum Herpetology Collection. 1627 records from RSPB - Bird survey records from RSPB's London House Sparrow Parks Project 2009-2010, covering 19 London parks and surrounding streets (Funded by SITA Trust, . 27 records from Hybridization in Umbridae in the Hudson River, New York, with Designation of Neotypes for Umbra limi and Umbra pygmaea.. 91 records from Birdrace-Die_TUErteltauben-Tübingen. 2 records from Stadtrand Berlin - Altglienicke/ Was krabbelt auf unserem Abenteuerspielplatz?. 511 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Invertebrados. 66 records from LK 11 im Mönchspark. 122 records from BIRDRACE INTERNETLITHO feat Fliegende Füchse. 6 records from Faunal assemblage of sediment core GS7603-11. 15 records from Abundance and composition of meiobenthos in surface sediments at Fladen Ground stations in August 1975, North Sea (Table 4). 78 records from Pollen profile from Pittsburg Basin. 1 records from Hornmilben (Oribatida) [pages 261 to 322]. 6103 records from Cumbria Biodiversity Data Centre - Norman and Florence Hammond records. Seawatch and coastal survey records.. 2174 records from MLZ Mammal Collection (Arctos). 2 records from On the female of Gypona reversa DeLong & Martinson, 1972, with emphasis on genital structures (Insecta: Hemiptera: Cicadellidae). 1 records from Oppiella signata, eine neue Art der Familie Oppiidae aus dem Osterzgebirge (Acari, Oribatei). 15 records from (Table 1) Carbonate constituents and quartz in the sand-sized fraction in Mississippi Fan sediments, DSDP Hole 96-615. 31506111 records from Artdata. 711 records from Odonata collection, NTNU, Trondheim. 2540636 records from Especímenes INBio. 2 records from Pantopoda SMF. 400 records from Colección Limnológica del Chocó. 6 records from Mammalia (JNHM-MM). 1896 records from Cnidaria Collection of the Seto Marine Biological Laboratory, Kyoto University. 115 records from RSPB - Bringing Reedbeds to Life Amphibian Survey of two key reedbed sites in England in 2010.. 104 records from Küstenschutzwald. 135 records from Kremmer Luch. 82 records from Paul-Gerhardt-Schule Dassel. 176 records from BIRDRACE Professorenteam. 510 records from Alterra (NL) - Microarthropods inventory in a range of forests. 1353 records from Colección de Entomología - Diptera - Ceratopogonidae. 1616 records from Gloucestershire Centre for Environmental Records - Gloucestershire Reptiles. 1 records from Nothrus segnis. 53 records from Royal Horticultural Society - Wisteria scale (Eulecanium excrescens) records acquired by the Royal Horticultural Society . 2 records from Simpsonichthys suzarti sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual fish from the Rio Pardo floodplains, northeastern Brazil.. 27988 records from Inventaire National du Patrimoine Naturel : Loup en France. 9787 records from Finnish Entomological Database: Hymenoptera. 2432 records from RSPB - Black Grouse Recovery Project Annual Survey in Argyll & Bute 2002-2009 (RSPB/SNH/FCS/Scottish Power). 7 records from Naturhausgarten. 8 records from Schutzgebiet Ochtersum. 15 records from Tiere und Pflanzen um uns herum !. 4 records from Stadtrandlandschaft Apolda-Nord. 10 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/314-1. 2 records from Ostracoda abundance of Hole 11-100. 5926 records from Insect (HUNM-IN). 240 records from Coleoptera identified from the Borax Works, Norman Road site, Bexley, London. 7 records from Artenvielfalt auf Zollverein. 67 records from Schiller Gymnasium Hof 10b. 33 records from Naturpark Kottenforst-Ville 17.6.09. 48 records from Wiesen in der Grünen Mitte. 48 records from (Appendix 7) Pollen analysis of soil profiles obtained in the Nagqu area. 8 records from Meiofauna abundance in sediment core 12930-018. 2 records from Benthic macrofauna abundance of sediment core 13077-019. 2792 records from Birds (UWEP-BI). 1428 records from Shellfish (GNHM-MS). 109 records from In situ observations of Stygiomedusa gigantea. 59 records from Succession of benthic hard-bottom communities abundance at station Errina2012_MDD3. 500 records from Anfibios y reptiles del municipio de Cuetzalan del Progreso, Puebla. 165 records from Australian National Herbarium (CANB). 9271 records from APIS - Antarctic Pack Ice Seals 1994-1999, plus historical data from the 1980's. 145103 records from EPA'S EMAP Database. 1678 records from Agriculture and Agri-Food Canada, St. Johns, Newfoundland. 1221 records from NBM Unionoids. 38049 records from CNMA/Colección Nacional de mamíferos. 2572 records from Mariposas (Lepidoptera: Papilionoidea) de la Colección Entomológica del Instituto Alexander von Humboldt. 2 records from The Erysiphales Collection at the Botanische Staatssammlung München. 15647 records from Universidad Autónoma de Madrid, Madrid; Lepidópteros. 2695325 records from Eremaea. 2 records from Oklahoma Vascular Plants Database Provider. 75 records from Streuobstwiese RSG (Cham). 89 records from Artenvielfalt auf den Elbwiesen (Dessau). 113 records from Schlichemquelle (Tieringen/Meßstetten). 147 records from Danisco-Wiese. 4960 records from NRM-Herpetology. 110 records from Coleoptera identified from the Horton Kirby site, near London. 19 records from Seeufer ehem. BUGA-Gelände. 4347 records from Aves Acuáticas en el Caribe Colombiano Entre 2007 y 2009. 63 records from Seawater carbonate chemistry and processes during experiments with coccolithophores (Emiliania huxleyi and Gephyrocapsa oceanica), 2000. 884 records from Asteroids from French subantarctic islands: records from the Marion Dufresne MD03 expeditions. 302 records from Stable oxygen and carbon isotope ratios of Globigerinoides obliquus of quantitative range chart of the ostracodes in the Pliocene-Pleistocene interval of ODP Hole 107-654A. 23 records from Nemertini - SMF. 857 records from Diversidad biológica y conservación del ecosistema de los perros de la pradera (Cymomys ludovicianus) en México. 199 records from La fauna de Melolonthidae, Cerambycidae y Elateridae (Insecta: Coleoptera) de la reserva de la biósfera El Triunfo, Chiapas. 1000 records from Avifauna de la reserva de la biosfera El Cielo, Tamaulipas, México. 7558 records from KNWR Entomology Collection. 16522 records from Shellfish specimens in the NISHINOMIYA SHELL MUSEUM, Japan.. 97 records from Korean Agricultural cari (Chelicerata). 10270 records from Museo Nacional de Ciencias Naturales, Madrid: Invertebrados Poliquetos. 70704 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1988) (AfrOBIS). 858 records from Mammalia - Baekdu Mountain Animal (KIDR-MM). 5 records from The Erysiphales Collection at the University Halle-Wittenberg. 365 records from Bird Specimens of Miyazaki Prefecture Museum of Nature and History. 16122 records from Colección Herpetológica del Museo de Zoología "Alfonso L. Herrera", México (MZFC, UNAM). 73 records from Entdeckertour am Muldestausee. 107 records from Bizzenbach-Aue im Bizzenbachtal (Wehrheim/Taunus). 120 records from Occurrence of mammalia relicts at site Euerwanger Bühl. 675 records from Collection Hydrozoa - ZSM München. 2406 records from Biodiversidad de la macrofauna bentónica en la microcuenca de Chabihau, Yucatán. 1616 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during two Michael Sars cruises in 2000. 17662 records from SeamountsOnline (seamount biota) (CoML). 3545 records from MICROBIS database. 3956 records from Royal Saskatchewan Museum Collection. 4749 records from CNAC/Coleccion Nacional de Acaros. 1636 records from Antarctic Echinoids: an interactive database. 53 records from Natur aus zweiter Hand am Muldestausee. 38 records from Frohlinder Mühlenbach (Dortmund-Kirchlinde). 7 records from Occurrence of mammalia relicts at site Salzgitter-Lebenstedt. 75 records from Occurrence of mammalia relicts at site Einhornhöhle. 30 records from Museu Paraense Emílio Goeldi - Solifugae Collection. 67 records from (Table 1) Ostracoda community from DSDP Hole 95-612. 40 records from Two new cichild species Neolamprologus (Teleostei: Cichlidae) from Lake Tanganyika, East Africa.. 23713 records from Pond Conservation - National Pond Monitoring Network collated pond survey data for Great Britain 1972 to 2007. 33 records from Astyanax endy (Characiformes: Characidae), a new fish species from the upper Río Bermejo basin, northwestern Argentina.. 42489 records from NCSM Herpetology Collection. 781 records from RSPB - Bittern Annual Surveys in Britain 1990-2008 (SCARABBS). 103 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Thamnophilidae. 1173 records from Aquatic Coleoptera Conservation Trust - SNH site condition monitoring of SSSIs for water beetles 2010. 6060 records from Free-living Nematodes from Patagonia coastal lagoons (Chubut, Santa Cruz, Argentina).. 2922 records from National Lesser Horseshoe Bat Database. 5729 records from Alterra (NL) - Entomofauna inventory in cattle grazed dune grassland. 13597 records from Orthopteroidea. 177454 records from CAS Entomology (ENT). 626853 records from Inventario Español de Especies Terrestres (MAGRAMA). 120208 records from Inventaire National du Patrimoine Naturel : Poissons d'eau douce de France. 324 records from Ostracoda in sediment core PS51/138-12. 346511 records from ARGOS Satellite Tracking of animals. 22771 records from Database Schema for UC Davis Wildlife museum. 1564 records from Auchenorhyncha collections of SW Finland. 28628 records from Marine invertabrate(Mollusca) specimen database of Osaka Museum of Natural History. 124 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 48 records from Schulgelände Dientzenhofer-Gymnasium (Bamberg). 11371 records from Mammal specimens. 69 records from Occurrence of mammalia relicts at site Ettingen. 44 records from Royal Horticultural Society - Pittosporum sucker (Trioza vitreoradiata) records acquired by the Royal Horticultural Society . 50 records from Countryside Council for Wales - Pearl Mussel distribution, Wales (2004-2012). 9962430 records from Norwegian Species Observation Service. 24681 records from Flea (Siphonaptera) Recording Scheme - Flea (Siphonaptera) Distributions in Britain and Ireland: pre 1975, 1975 onwards. 30999 records from MSB Bird Collection (Arctos). 6645 records from Ephemeroptera of Ireland. 102 records from Sipuncula collection of National Museum of Nature and Science. 94 records from Artenvielfalt im Beckerbruch (Dessau). 2 records from Range table from ostracoda in ODP Hole 159-960A. 24 records from Taxonomy and phylogenetic relationships among species of the seasonal, internally inseminating, South American killifish genus Campellolebias (Teleostei: Cyprinodontiformes: Rivulidae), with the description of a new species.. 9 records from Benthic macrofauna abundance of sediment core 13200-073. 30 records from Aktionstag Wiese am Vogelhammerkopf. 64 records from Lissarca notorcadensis. 1 records from Cepheus minutus. 3 records from Akita Prefectural Museum＋Millipedes Specimens of Akita Prefectural Museum. 15309 records from SOMBASE. 5264 records from Gulf of Maine Bottom Trawl Survey Data (NEFSC,NMFS,NOAA)(USOBIS). 39333 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 2004) (AfrOBIS). 26375 records from Provincial Museum of Alberta, Edmonton, AB, Canada. Birds (Aves). 105 records from Occurrence of mammalia relicts at site l´Abri de la Ferrassie. 2042 records from Butterflies and Skippers of Alberta Project. 41 records from Cameroon National Herbarium. 25 records from Muehlenbach bei Friesheim. 1 records from A new species of the genus Comaroma in China (Araneae: Anapidae). 26 records from Composition of benthic macrofauna in surface sediments of the east Greenland continental slope (75° N section). 3 records from Colección de Herbario. 9123 records from IICT Colecção Zoológica. 1101 records from Colección de Entomología - Orthoptera. 1 records from Arthropoden aus südostalpinen Höhlen.. 561820 records from Bee Biology and Systematics Laboratory. 654 records from Helgeland Museum, Tabanidae. 27 records from Regenwasserabfangbecken. 192 records from (Appendix A) Radiolarian abundances in sediment core MD96-2086. 26 records from Kindervilla Aussengelände/ Hiltroper Park. 1323 records from Estación Experimental de Zonas Áridas (CSIC), Almería: EEZA-Ungulados. 86 records from Pollen analysis of sediment core GIK16856-2. 88 records from North-west Ireland Machair Breeding Waders 2009.. 3578 records from RSPB - Bird Conservation Targeting Project (BCTP) in the UK, 2004-2009 â sensitive records. 10064 records from The Deepwater Program: Northern Gulf of Mexico Continental Slope Habitat and Benthic Ecology - DgoMB: Macrofauna. 63349 records from Marine and Coastal Management - Linefish Dataset (First Semester of 2001) (AfrOBIS). 134 records from Schulhof Goethe-Gymnasium (Emmendingen). 34 records from Occurrence of mammalia relicts at site Fohlenhaus-Höhlen. 26 records from Abundance of epibenthic echinoderms at seafloor photography station PO196_1008. 718078 records from Insect (KNAM-IN). 43 records from Description of a new species of weasel shark, Hemigaleus australiensis n. sp. (Carcharhiniformes: Hemigaleidae) from Australian waters.. 194 records from Kiesbagger (Mittelhausen). 14 records from Occurrence of mammalia relicts at site Barrington. 1 records from Range table from benthic foraminifers in ODP Hole 151-913B. 207003 records from Banco de Datos de la Biodiversidad de la Comunitat Valenciana. 1099915 records from DOF 2001-2006. 99159 records from Biological Records Centre - Dragonfly and Damselfly (Odonata) records for Britain to 1992, from the former Dragonfly Recording Scheme. 8 records from A taxonomic revision of the Asian endemic subgenus Physocrema of the genus Crematogaster (Hymenoptera: Formicidae).. 8008 records from Avistajes de espcies de valor especial en áreas protegidas del noreste de Argentina. 40 records from National System of Protected Areas in Poland - Plants. 1180 records from Birds fallen at Danish Lighthouses 1883 through 1939. 9 records from Two new species of Elacatinus (Teleostei: Gobiidae) from the Mexican coast of the Gulf of Mexico.. 364496 records from Bishop Museum Natural Sciences Data. 31 records from (Table 4) Abundance of under-ice amphipods on flat ice and ice ridges sampled during the 2005 Hidden Ocean expedition. 74 records from Macrofauna abundances from mesocosm experiments at eastern and western branches of the Whittard canyon. 765 records from Colección de peces marinos del mar argentino y aguas adyacentes del INIDEP. 1 records from Il popolamento dell'Appennino meridionale: dall'Appennino campano alle serre calabre. Osservazioni sui chilopodi dell'Appennino lucano e calabrese (Chilopoda). 113 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña noviembre 2006. 44802 records from Insect collection of Biodiversity Center of Japan, Ministry of the Environment. 17421 records from Arthropod collection, Tromsø Museum. 6314 records from UWYMV Mammal Collection (Arctos). 18501 records from Biological Records Centre - Lacewings and allied insects records from Britain and Ireland to 1999. 1 records from Miriapodi di alcune grotte della Campania. 3087 records from Herpetile collection, Natural History Museum, University of Oslo. 9 records from Polyrhachis (Myrma) cyaniventris F. Smith, 1858 (Hymenoptera: Formicidae) and a related new ant species from the Philippines.. 3 records from Selenops muehlmannorum spec. nov. from Southern Laos (Araneae: Selenopidae). 38 records from Fourteen new species of Pseudisobrachium (Hymenoptera, Bethylidae) from Atlantic rain forest of Espírito Santo, Brazil.. 115 records from Artenvielfalt Kreis Gießen. 39 records from (Table III) Abundance of crustacea orders during RSS James Clark Ross cruise JR144. 5616 records from COMARGIS: Information System on Continental Margin Ecosystems. 42369 records from Collection Aves (bird skins) SMF. 121 records from Southern Giant Petrel census data within the Australian Antarctic Territory.. 596 records from Distribution of generalized biologic, anthropogenic, and volcanic constituents in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 3500 records from Colección Ictiológica de la Universidad de Antioquia. 26 records from Akysis pulvinatus, a new species of catfish (Siluriformes: Akysidae) from southern Thailand.. 1 records from Damaeus auritus. 4 records from Evidence for the continued presence in New Zealand of Homotrysis macleayi (Borchmann, 1909) (Coleoptera: Tenebrionidae: Alleculinae). 2 records from Studies on the ant fauna of Melanesia V. The tribe Odontomachini.. 12 records from (Table 1) Length, weight, fat content and age of Norwegian spring spawning herring (Clupea harengus) during 2007. 1562 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña enero 2011. 16751 records from Tachinid Recording Scheme - Tachinid Recording Scheme - GB and Ireland records. 6 records from Fundulopanchax kamdemi (Cyprinodontiformes: Nothobranchiidae) a new species from Korup National Park, western Cameroon.. 2772 records from Helgeland Museum, Araneae. 617129 records from Historical Bird Atlas. 2 records from Discothyrea sringerensis (Hymenoptera: Formicidae) a new ant species from India.. 12 records from Herbario CDMB - Jardín Botánico Eloy Valenzuela. 54 records from Three new species of Gastromyzon (Teleostei: Balitoridae) from southern Sarawak.. 3893 records from DMNS Marine Invertebrate Collection (Arctos). 41 records from Insektenvielfalt Ahe/Weichelsee. 27 records from Mühlenbach bei Buxtehude. 136 records from Bernhardsthal. 89 records from BIRDRACE Hasenclevers Erben - NaBu-Bi-BirdRace-Open. 1087 records from The Bat Conservation Trust - Bechstein's Bat Survey Project. 58061 records from North & East Yorkshire Ecological Data Centre - North and East Yorkshire Ecological Data Centre - Non-sensitive Records from all taxonomic groups. . 94 records from Gieselbachtal Fulda-Harmerz. 267212 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 4 records from Distribution of meiobenthos in sediment core M19_263 of the northeastern Atlantic (Table 1). 1 records from Wildnis Erzental. 4 records from BB-Biodiversität a. 37 records from MfN - Fossil plants (Cenophytic). 259 records from MfN - Fossil plants (Mesophytic). 11 records from Benthic macrofauna abundance of sediment core 13077-063. 9 records from Benthic macrofauna abundance of sediment core 13200-045. 30534 records from Insect Collection from the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 253 records from (Table 2) Occurrence of ostracoda in sediment core PS2200-5. 14 records from 2. Aspacher GEO-Tag der Artenvielfalt. 5 records from Plant (NSMK-PL). 43 records from Species occurring in the mytilid and alvinellid communities within the 9°N hydrothermal field at the East Pacific Rise. 1873 records from Collection Bernstein - SMF. 53 records from Fonoteca Zoológica, Museo Nacional de Ciencias Naturales, Madrid: FZ_REPTILIA. 75706 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1991) (AfrOBIS). 34630 records from Herpetology. 234 records from Philosophenwald und Wieseckaue in Gießen. 64 records from Schulhof und Anlagensee in Nellingen. 57 records from Unser kleines Rasenstück/ Dürer-Gymnasium Nürnberg. 478 records from Occurrence of mammalia relicts at site Raj Cave. 131 records from Occurrence of mammalia relicts at site Geißenklösterle. 26 records from Occurrence of mammalia relicts at site Bedburg-Königshoven. 33 records from Occurrence of mammalia relicts at site Wildenscheuer Cave. 17 records from Occurrence of mammalia relicts at site Felslindlhöhle. 22 records from Occurrence of mammalia relicts at site Climauti II. 16444 records from DORSA - German Orthoptera Collections. 72 records from Schwanheimer Wald. 3864 records from Mammal specimen database of Kanagawa Prefectural Museum of Natural History. 91382 records from Collection Mammalia SMF. 18 records from Hangwiese bei Tussenhausen Klassen 1 a und 1 b. 56 records from Landschaftspark St.Leonhard-Deisendorf. 32 records from Alter Lagerplatz und Gartenteich (Dortmund/Hörde). 104 records from BIRDRACE Erlanger Piepmätzchen. 2905 records from A checklist to the wasps of Peru (Hymenoptera, Aculeata). 41 records from NSG Forst Zinna-Jüterbog-Keilberg. 8 records from Landschaftsschutzgebiet Buchhorst2. 271467 records from Biological Records Centre - Database for the Atlas of Freshwater Fishes. 20 records from Ostracoda abundance of Hole 42-376. 965 records from Northumberland Wildlife Trust - Squirrel Records for 2002 - 2005. 8 records from Meiofauna abundance in sediment core 13077-058. 2 records from AlgaTerra. 734 records from Mammals (NSMK-MM). 31 records from Pollen record of sediment core Bokanjacko Blato 2. 1000 records from Colección de los peces nativos de Sonora. 4100 records from Actualización de la base de datos de crustáceos de la Colección Biológica de la Secretaría de Marina. 115 records from Mollusca specimens of Kuroshio Biological Research Foundation. 16233 records from Crustacea specimens of Toyama Science Museum. 1 records from Jardín Botánico de Córdoba: Herbarium COA. 682810 records from NODC WOD01 Plankton Database. 1513 records from M. Gollop Collection. 362 records from Northern Forestry Centre Arthropod Collection, Edmonton. 321 records from STAMP seabird egg collection. 26 records from Algaterra Types. 917 records from Northern Barrier Marine Life (OBIS Australia). 25 records from Antarctic Krill occurrence data from Spanish RV "Fruela". 186 records from Freiburger Tag der Artenvielfalt. 191504 records from Joint Nature Conservation Committee - Marine benthic dataset (version 1) commissioned by UKOOA. 131314 records from Biological Records Centre - Mammal records from Britain from the Atlas of Mammals (1993), with some subsequent records. 2 records from Pollen analysis of sediment profile SI0 from Siethener See. 3 records from Distribution of meiobenthos in sediment core M23_149 (2) of the northeastern Atlantic (Table 1). 116 records from MfN - Fossil vertebrates I. 54 records from Macrofauna abundance in surface sediment sampled during cruise DI226. 241 records from Macrobenthos in surface sediments off Sylt collected during Heincke cruise HE218. 1 records from Mesozoa - SMF. 8 records from Crustacea in surface sediments off Sylt collected during Heincke cruise HE206. 1939 records from Biodiversidad de moluscos opistobranquios (Mollusca: Opisthobranchiata), del Pacífico mexicano: Isla Cedros-Vizcaíno e islas del Golfo de California parte Sur. 22183 records from Análisis de las relaciones entre las diversidades alfa, beta y gamma a distintos niveles de escala espacial: Procesos históricos y ecológicos que intervienen. V Etapa. 517 records from Inventario de los murciélagos de los parques nacionales Sierra de San Pedro Mártir y Constitución de 1857, Baja California, México. 2588 records from A comparison of benthic biodiversity in the North Sea, English Channel and Celtic Seas (EurOBIS). 16600 records from Fish Specimens of Museum of Tokushima Prefectural Museum, Japan. 91 records from CNIN/Tipos Homoptera. 80 records from Botanischer Garten (Saarbrücken). 1 records from Occurrence of mammalia relicts at site Kleine Feldhofer Grotte. 234 records from CNMA/Colección de Mamíferos de la Estación de Biología Chamela. 763 records from Bisons Collection. 1145 records from Colección de Anélidos. 86633 records from Entomological collections, UiB. 6 records from Artenvielfalt am "Grünen Band" bei Coburg: 20 Jahre Wiedervereinigung. 38 records from Streuobstwiese Stedar 2009. 14 records from Hessen-GEO-Tag am Schlossberg von Homberg/Efze. 976 records from Colección de Entomología - Coleoptera. 312 records from CréBeo Earthworm Records 2006/7. 252 records from Systematics, distribution and biology of the Australian ' micro-flea' wasps, Baeus spp. (Hymenoptera: Scelionidae): parasitoids of spider eggs.. 156 records from Portuguese Seaweeds. 39 records from University Marine Biological Station Millport - 1995 EC Study Contract Clyde Sea Nephrops Stock Assessment Study. 5287 records from Diptera collection (ED) of the Muséum national d'Histoire naturelle (MNHN - Paris). 7 records from Nationalpark Harz Schul-AG Braunlage. 10 records from Ökowerk Emden. 12 records from Hache im Ellernbruch (Sudweyhe / Weyhe). 28 records from Fürstenberger Ralley Teil 3. 82 records from Results of the pollen analysis of the Dyanushka peat sediments K7/P2. 516 records from Artenvielfalt am Eich-Gimbsheimer Altrhein. 385 records from Macrobenthos in surface sediments off Sylt collected during Heincke cruise HE262. 12006 records from UAM Invertebrate Collection (Arctos). 1 records from Field Museum of Natural History (Botany) Seed Plant Collection. 135656 records from RSPB - Bird Conservation Targeting Project (BCTP) in the UK, 2004-2009. 2012 records from Caracterización morfométrica del bagre rayado para la cuenca del Magdalena. 28277 records from Herts Bird Club - Hertfordshire Breeding Bird Atlas : 1988-1992. 4 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 1 records from Die Myriopodenfauna von Albanien und Jugoslavien. 10306 records from RSPB - Bringing Reedbeds to Life Invertebrate Survey of three key reedbed sites in England in 2009, 2010. RSPB led project with 50% funding from Natural Engl. 336 records from Especies de Anacroneuria (Insecta: Plecoptera: Perlidae) de Colombia, depositadas en el Museo de Entomología de la Universidad del Valle (Cali, Colombia). 7464 records from Merseyside BioBank - North Merseyside Reptiles and Amphibians (unverified). 5053399 records from Southern African Bird Atlas Project. 1658 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña enero 2009. 45 records from Global Lacustrine Diatoms. 47 records from Kloster Eberbach. 24 records from Balkon (Norderstedt). 6325 records from Colección Entomológica de la Universidad de Antioquia. 16087 records from RSPB - Corncrake national surveys - territory centres (SCARABBS). 2 records from Abundance of benthos infauna at station PS1239-1. 128873 records from Ground Beetle Recording Scheme - Carabid data for Great Britain from the Ground Beetle Recording Scheme held by BRC. 278 records from A review of the species in the Apogon fasciatus group with a description of a new species of cardinalfish from the Indo-West Pacific (Perciformes: Apogonidae).. 18 records from (Table 2) Megafauna density 2002, 2004 and 2007 in the deep-sea observatory AWI-HAUSGARTEN, Fram Strait. 17 records from Type herbarium, Göttingen (GOET). 70087 records from Insect Occurrence Data from MIZA. 57 records from A new Stomatorhinus (Osteoglossomorpha: Mormyridae) from the Ivindo River, Gabon, West Central Africa.. 5 records from Description of two new Temnothorax species (Hymenoptera: Formicidae) from Italy.. 73 records from Norwich Reptile Study Group - Norwich Reptile Study Group Records for 2011. 22681 records from Museu Paraense Emilio Goeldi - Araneae Collection. 65 records from Revalidation and redescription of Pterocryptis anomala (Herre, 1933), a catfish (Teleostei: Siluridae) from southern China.. 6 records from Hemichordata collection of National Museum of Nature and Science. 74 records from Terrestrial gastropods of Srebarna Nature Reserve, North-Eastern Bulgaria ( Gastropoda ). 7693 records from NHM, Heteroptera. 5 records from Oribatid mites from Switzerland, IV (Acari: Oribatida: Suctobelbidae). 266 records from Nematode abundance in cold seep sediments of the Nordic Margins (Nyregga, Styregga, Haakon Mosby Mud Volcano). 63 records from Revision of the ant genus Myrmoteras in the Malay Archipelago (Hymenoptera, Formicidae).. 649 records from Countryside Council for Wales - Great Crested Newt (Triturus cristatus) Sites in Wales to 2003. 226 records from (Table A1) Annual biomass of plants and animals recorded on Bylot Island between 1993-2009. 133 records from (Table 2) Species density and composition of an inshore and offshore station in Kongsfjord, Svalbard. 31 records from Finnish Entomological Database: Blattodea. 322 records from Collections ichtyologiques et herpétologiques (BOUM). 154 records from (Table 2b) Biomass of macrobenthos species in samples from Cruise AMK54 stations in the Novaya Zemlya Trough. 157 records from Die Oribatiden-Arten (Acari) eines suedwestdeutschen Buchenwaldes I.. 320 records from Scottish Wildlife Trust - Ants: Formica Exsecta Records from Abernethy RSPB. 1134 records from Alterra (NL) - Microarthropods inventory in European countries. 3873 records from Littoral Macroinvertebrate data from Irish lakes. 1 records from Arthropoden aus südostalpinen Höhlen.. 6 records from University of Amsterdam (NL) - Páramo Vegetation Research, Sumapaz-Bocagrande-Chisaca paramo complex, Colombia. 1866 records from Colección de Crustacea del Museo Nacional de Historia Natural de Chile. 13 records from (Table T2) Benthic foraminfera stratigraphy of ODP Hole 199-1220B sediments. 1948 records from CCBER Mammalogy Collection. 108 records from Birdrace-TriumVIErat-Viersen. 8 records from University of British Columbia Herbarium (UBC) - Lichen Collection. 8 records from Auf Feld und Wiese / Bretlebener Weg (AWO - Kita Heldrungen). 79 records from Waldi-Weiher. 91 records from BIRDRACE SchrägeVögel. 7320 records from Aves Collection of Institute of Systematics and Evolution of Animals. 3 records from Arthropoden aus südostalpinen Höhlen.. 15818 records from Amphibians and Reptiles collection at the Natural History Museum of Denmark (SNM). 27436 records from Vegetation data from protected areas in Denmark (§ 3 in the Danish Nature Protection Act). 15 records from NOTE SU ALCUNE SPECIE DEL GEN. EUPOLYBOTHRUS DELLA FAUNA DI GRECIA (Chilopoda, Lithobiomorpha). 152 records from Investigación y manejo para la conservación de tortugas amenazadas de los humedales llaneros. 104943 records from Countryside Council for Wales - Welsh Peatland Invertebrate Survey (WPIS). 263329 records from European Seabirds at Sea (ESAS) bird sightings from 1980 to 2003.. 359 records from Lepidoptera collection (EL) of the Muséum national d'Histoire naturelle (MNHN - Paris). 155 records from Megophthalmidia_of_North_America. 24 records from (Tables 1,2) Site characteristics and phenotypic attributes of King Penguins (Aptenodytes patagonicus) on Possession Island. 37 records from Höltigbaum. 8 records from Mit allen Sinnen durch den Wald / Schmücke (ev. Kita Heldrungen). 55 records from Artenvielfalt im Naturschutzgebiet an der Loreley - Leiselfeld/Spitznack - 2. Jahr. 23 records from Artenerfassung für Jedermann in der Grundschule Kirchboitzen. 106 records from Sylter Meerstrandläufer. 177 records from BIRDRACE Die Kielbris. 2699 records from Coleópteros del Centro del Estado de Veracruz, de Palenque, Chis. y de la Sierra de Manantlán en Jalisco y Colima, México (IE-XAL). 2518 records from Natural History Museum Rotterdam (NL) - Invertebrata miscellaneous Collection. 3 records from Redescription of Lystrocteisa Simon, 1884 (Araneae: Salticidae) from New Caledonia. 1115 records from Upper Silesian Museum, Insect Collection. 2 records from Amphibia ZMK. 1 records from Nothrus bispinosus. 2259055 records from Museum of Comparative Zoology, Harvard University. 1594 records from Musée Vert ornithology collection. 60 records from (Appendix A) Palynofacies absoulte abundances of DSDP Hole 38-338. 96 records from WildesMoor bei Schwabstedt. 4 records from Ohemoor (Hamburg/Norderstedt). 214 records from Natur-Erlebnisgebiet der Naturschutz-Akademie Hessen und Umgebung. 4 records from Herbarium specimens of Société des Sciences Naturelles et Mathématiques de Cherbourg (CHE). 25 records from Numbers and dry weights of meiobenthos taxa in surface sediments at Fladen Ground station 1, North Sea (Table 6). 2 records from Distribution of meiobenthos in sediment core M23_123 (2) of the northeastern Atlantic (Table 1). 62 records from Faunal assemblage of ODP Hole 101-633A (Table 1). 1864 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 31 records from Macrofauna biomass in surface sediment sampled during cruise DI231. 53482 records from Northern Territory Museum and Art Gallery provider for OZCAM. 16632 records from BANDAPHO, BAse de DAtos sobre Aphodiidae. 1 records from Sungei Buloh - Mangrovenwald. 10 records from Wasserbachsee. 17 records from Molluscs in surface sediments off Sylt collected during Heincke cruise HE258. 1660 records from Revisión de la subfamilia Asopinae (Hemiptera-Heteroptera-Pentatomidae) para México. 333 records from Límites de especies dentro del género Gerrhonotus (Sauria: Anguidae). 20 records from Tongrube bei Hettstedt. 95 records from Nematode densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC09. 108 records from Baggerseen bei Krauchenwies. 104 records from Butterberg, Dardesheim. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 172 records from Collection Crustacea NHCY. 128 records from Grünes Germersheim. 4601 records from Insect (NHMK-IN). 4 records from The Lichen Collection at the Botanische Staatssammlung München. 465 records from (Table 5) Pleistocene ostracodes from ODP Hole 104-644A. 158 records from Polychaetes in surface sediments off Sylt collected during Heincke cruise HE241. 2109 records from Helmintos de peces dulceacuícolas de México. 6414 records from Colección de referencia de vectores de Leishmania spp (causante de Leshmaniasis cutánea localizada) de la Península de Yucatán y un estudio preliminar en un área endémica de Quintana Roo. ECOSUR_SNIB. 22 records from Collection Mantodea - SMF. 2 records from British Lichen Society - BLS Lichen Database: Scotland. 23202 records from Gwaii Haanas Invertebrates (OBIS Canada). 894 records from CNAN/Arañas sinantrópicas. 822 records from Amphibian and Reptile (NMNO-AR). 19 records from Distribution Data for Megachile chomskyi. 6 records from "Wildnis erleben" - "Vielfalt erlebbar machen" - Botanischer Garten u.Chrimmitschauer Wald. 19 records from Liether Park (LMS), 6c. 2 records from Benthic macrofauna abundance of sediment core 12930-063. 7 records from Benthic macrofauna abundance of sediment core 13077-089. 936 records from RMT Trawl catch from the 1982/83 V2 ADBEX I voyage. 2255 records from Evaluación de la ictiofauna en las áreas focales del corredor biológico costero-Yucatán. 3912 records from Röntgenarchiv Wilhelm Stürmer - SMF. 68539 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1994) (AfrOBIS). 51 records from Occurrence of mammalia relicts at site Bocksteingrotte/Lonetal. 3119 records from Hormigas en cultivos de naranja (Citrus sinensis (L.) Osbeck) de la costa Caribe de Colombia. 3 records from UA Herbarium. 70 records from Exotic terrestrial flatworms, Macquarie Island. 3207 records from Collection Echinodermata SMF. 2 records from Abundance of benthos infauna at station GIK23043-2. 40316 records from The Scottish Ornithologists' Club - Clyde Breeding Bird Tetrad Atlas 1985 - 1991 - non-sensitive species. 114 records from RSPB - Tree sparrow recovery project â summary data, North West England, 2004-2010 (RSPB, NE, Wirral Borough Council, Cumbria Biodiversity Partnership). 7118 records from MUST, Insecta. 26 records from Akysis longifilis, a new species of catfish (Teleostei: Akysidae) from Myanmar.. 120 records from Paleontological collection of the National Museum - Flora. 4003123 records from OEH Atlas of NSW Wildlife. 124 records from Pollen profile from Samerberg 2. 458 records from Estado actual del conocimiento biológico de algunas especies de roedores de las familias Muridae, Geomyidae, Heteromyidae y Sciuridae (Rodentia: Mammalia) incluidas en el PROY-NOM-059-ECOL-2000. 228 records from Colección de Quelonios Museo de La Salle Bogotá (MLS). 1514 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise DeHolland1986. 1130 records from ISU Mammals. 7 records from Ostracod abundance in sediment core Lz1120. 299 records from Korean Insect Database (Hymenoptera: Ichneumonidae). 963 records from University of Western Ontario Collection. 75089 records from SDNHM Herpetology Collection. 234 records from Antarctic Krill occurrence data from Australian expeditions. 84 records from Naturschutzstation Schmidsfelden. 135 records from Birdrace_Dith_MarshSandpiper-Dithmarschen. 778 records from Apterygota collection (EA) of the Muséum national d'Histoire naturelle (MNHN - Paris). 1 records from Range table from benthic foraminifers in ODP Hole 143-866A. 8 records from Oberservation of birds at station PS14/143 along 49° West. 2 records from Herbarium of Taiwan Forestry Research Institute. 5714 records from Insect Arthropods (KIDR-IN). 749 records from Carabidae of Wales and England. 15 records from Pogonophora collection of National Museum of Nature and Science. 1178 records from Birds (NMNO-BI). 5056 records from Respaldo de las colecciones de tejidos del Museo de Zoología, Departamento de Biología Evolutiva, Facultad de Ciencias, UNAM (Aves). 7602 records from Finnish Entomological Database: Trichoptera. 6 records from (Appendix B) Analyses of sulfides of ODP Leg 121 basalts. 5914 records from Swiss Psyllid (Hemiptera) Collections - Geneva. 2 records from Herbarium, Botany Unit, Finnish Museum of Natural History (H). 3041 records from Electronic Atlas of Ichthyoplankton on the Scotian Shelf of North America (OBIS Canada). 9674 records from Mammal collection of National Museum of Nature and Science. 15 records from Staatliches Museum für Naturkunde Stuttgart, Herbarium. 192 records from Administración Nacional de Institutos y Laboratorios de Salud. 46400 records from Museu Paraense Emilio Goeldi - Ophidia Collection. 72316 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1993) (AfrOBIS). 87 records from Antarctic Euphausiacea occurence data from Polish FIBEX expeditions. 10 records from Occurrence of mammalia relicts at site Aveley. 32 records from Occurrence of mammalia relicts at site Pecurski Karnen. 18 records from Occurrence of mammalia relicts at site Niederlehme. 5 records from Occurrence of mammalia relicts at site Mitoc Malul Galben. 49 records from Additional records for Stenosagola newtoni Park & Carlton, 2013 (Staphylinidae: Pselaphinae: Faronitae), with notes on aedeagal morphology. 1 records from Pelops phaeonotus. 539 records from Bay of Puck dataset (EurOBIS). 31157 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 2003) (AfrOBIS). 1 records from Hoplophora lentula. 61365 records from Colección Ornitológica del Museo de Zoología 'Alfonso L . Herrera', México (MZFC, UNAM). 29 records from Schulgelände (Wetter). 87 records from Trockenrasen und Buchenwald in der Umgebung der Jugendherberge Bad Blankenburg. 123 records from Birdrace-SportfreundeTriller-Münster. 4 records from Occurrence of mammalia relicts at site Erbiceni. 9 records from Oberservation of birds at station PS14/142 along 49° West. 1 records from Abundance of benthos infauna at station PO128/2_284. 661 records from Dumfries & Galloway Nightjar Study Group - Nightjar breeding season surveys in Dumfries and Galloway between 1981 and 2009 (Dumfries and Galloway Nightjar Study Group). 3447 records from Lepidoptera collection of NW Europe. 306 records from Camera trap database of Tiger from Rajaji National Park, Uttarakhand. 3857 records from Derbyshire Wildlife Trust - Derbyshire Wildlife Trust Odonata Records up to Dec 2012. 22749 records from Mollusk data of Molltax, Norway. 76823 records from Conchological Society of Great Britain & Ireland - Mollusc (marine) data for Great Britain and Ireland. 47499 records from Sphaeroceridae Collection. 151 records from Molluscan fauna of Gueishan Island of Taiwan. 63 records from (Table 2) Ostracoda community from DSDP Hole 95-613. 4167 records from Derbyshire Wildlife Trust - Derbyshire Wildlife Trust Coleoptera Records up to Dec 2012. 124 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 50 records from Isartal Dingolfing. 6 records from Faunal assemblage of sediment core TR149-35. 36 records from A revision of the genus Medmassa Simon, 1887 (Araneae: Corinnidae) in the Afrotropical Region. 17 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/357-1. 96591 records from Image Database of Fishes in the Kanagawa Prefectural Museum of Natural History. 6 records from Two new species of deeper dwelling Apogon (Perciformes: Apogonidae) from Micronesia and South Pacific Ocean.. 521 records from BUND - Dassower See (Lübeck/Dassow). 4 records from Occurrence of mammalia relicts at site Ahlen. 31 records from Occurrence of mammalia relicts at site Gamssulzenhöhle. 50 records from ANDEEP3: SeaStars (Echinodermata, Asteroidea). 1219 records from Coleoptera of Biebrza National Park. 1 records from Campylomorphus homalisinus (Elateridae): a new species for Lombardy (Italy), with notes on its ecology, distribution and biogeography. 2 records from First record of Pyramica baudueri (EMERY, 1875) (Hymenoptera: Formicidae) from Bulgaria.. 64322 records from AUM Fishes Collection. 1421 records from Weevils of Poland. 4676 records from Butterflies of County Waterford. 954 records from Visfauna - Juvenile and adult fishes in riparian habitats along the river Leie. 279 records from Dieta del Piquero Café (Sula leucogaster etesiaca) en el Parque Nacional Natural Gorgona, Pacífico colombiano.. 27440 records from The Environmental Sample Collection of the Arthropoda Varia Section at the Zoologische Staatssammlung München. 1 records from University of Amsterdam (NL) - Páramo vegetation research, Ecuador.. 2 records from Pollen analysis of sediment profile AUL00 from Steeger See. 11510 records from Merseyside BioBank - North Merseyside Insects (verified). 52 records from The high alpine bee fauna (Hymenoptera: Apoidea) of the Zillertal Alps, Austria. 154 records from Specimens from India at the NTNU University Museum in Trondheim. 1 records from Identification of the species of Gnamptogenys Roger in the Americas.. 9 records from Corumbataia britskii (Siluriformes: Loricariidae: Hypoptopomatinae) a new species from the upper Rio Parana basin, Mato Grosso do Sul, Central Brazil.. 23 records from Description of Cathorops manglarensis, a new species from the Colombian Pacific, with redescription of Cathorops multiradiatus (Siluriformes; Ariidae).. 416 records from Type Collection of the Seto Marine Biological Laboratory, Kyoto University. 1733 records from Birds collection of Abiko City Museum of Birds. 69 records from Revision of the subgenus Aulacomyrma Emery of the genus Polyrhachis F. Smith, with descriptions of new species.. 144 records from Whale Observations from the British, Australian and New Zealand Antarctic Research Expedition (BANZARE) voyages 1929-30 and 1930-31. 553 records from EcoRecord - Leech (Hirundenea) records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 6 records from Pseudogramma xanthum, a new replacement name for a serranid fish from the subtropical South Pacific Ocean with description of the species.. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 84 records from (Figure 2) Foraminifera in lower to middle Albian sediments of DSDP Hole 80-549. 4714 records from Coleccin de Anfibios. 37090 records from Instituto de ciencias naturales. 32152 records from Invertebrata Collection of Institute of Systematics and Evolution of Animals. 471 records from British Bryological Society - Bryophyte data for Great Britain from the British Bryological Society held by BRC. 1 records from Oribates fuscipes. 38 records from The Oriental species of the ant genus Probolomyrmex (Insecta: Hymenoptera: Formicidae: Proceratiinae).. 41 records from Studies on the Zoarcidae of the southern hemisphere. X. New records from western Antarctica.. 5 records from Ventichthys biospeedoi n. gen. et sp. (Teleostei, Ophidiidae) from a hydrothermal vent in the South East Pacific.. 1894 records from Aves Playeras y Otras Aves Asociadas a Arrozales en los Departamentos de Casanare y Meta en 2009 - 2010. 9 records from University of Amsterdam (NL) - Páramo vegetation research, Western Andean Cordillera. 1 records from (List 1) Summary of fossil Mollusca found in Schleswig-Holstein, Germany. 54207 records from TNHC Ichthyology Collection. 122 records from Birdrace_Gütersloher_Gimpel-Gütersloh. 103 records from Birdrace-Die_Nachtigallen-Herford. 73 records from Zielbach (Töll). 104 records from Spießwoogtal / Königsbruch (Fischbach). 24 records from Schulgelände Hans-Carossa-Gymnasium (Berlin). 269 records from BIRDRACE Kosmos-Racer. 16 records from Schulteich Regionales Förderzentrum "J.H. Pestalozzi" Sondershausen. 11168 records from Akita Prefectural Museum:Hiroki Watanabe Collection of mollusca. 55 records from Revisionary studies on the attine ant genus Trachymyrmex Forel. Part 3: The Jamaicensis group (Hymenoptera: Formicidae).. 125050 records from Natural History Museum Rotterdam (NL) - Insecta collection. 1 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Formicariidae. 7288 records from Thames Valley Environmental Records Centre - Local Wildlife Site Surveys Oxfordshire. 123005 records from Finnish Entomological Database: Diptera. 519006 records from Museum Victoria provider for OZCAM. 1232 records from The Fossil Fish Collection at the Bayerische Staatssammlung für Paläontologie und Geologie. 21595 records from Monitoring data from the federal state Mecklenburg-Western Pomerania (Germany). 12 records from Ludwigshofen. 1 records from Living benthic foraminifera at station M33/1_MC-13 (WAST-T), size fraction 63-125 µm. 368 records from RSPB - Ring ouzel national sample survey in the UK in 1999 (SCARABBS). 19 records from Cottus kanawhae, a new cottid fish from the New River System of Virginia and West Virginia.. 345 records from (Table T2) Biogenic and mineral composition of sediments cored in Vaale, Schleswig-Holstein. 12 records from (Table 1.2.2.1) Integrated abundance of sympagic meiofauna in sea-ice cores of Polarstern cruise ANT-XXIII/7. 279456 records from UWFC Ichthyology Collection. 3 records from CABI Bioscience Genetic Resource Collection. 7926 records from NBM birds. 13 records from Results of palynological analysis of Hole 302-M0004A. 22 records from (Tab. 13) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 32-306, Shatsky Rise southeast of Japan. 17557 records from Orthoptera collection of Hiratsuka City Museum. 71 records from Benthic meiofauna abundance in surface sediment of core PLG93_BCORE5. 7047 records from SMNS Herpetologie. 572 records from Zooplankton (NSMK-ZP). 9 records from Austrolebias univentripinnis sp. nov. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual killifish from the Mirim Lagoon basin, southern Brazil.. 7 records from Micralestes (Characiformes, Alestidae) of the lower Congo River, with a description of a new species endemic to the lower Congo River rapids in the Democratic Republic of Congo.. 7 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Melanopareiidae. 3422 records from The Scottish Ornithologists' Club - Highland Breeding Bird Data 2002-2003 - non-sensitive breeding species. 26 records from Junge Heide, Radebeul/Dresden. 79 records from Birdrace-Bielefinken-Bielefeld. 5 records from Feuchtwiese. 76 records from BIRDRACE Nachtigallen. 74295 records from Bees of Ireland. 14 records from Range table from ostracoda in ODP Hole 160-967A. 174 records from Collection malacologique Henri-Lecoq. 230 records from Sistematización de la Colección Paleontológica de la Facultad de Ingeniería, UNAM. 4 records from BCCM/LMG - Laboratory of Microbiology Gent Bacteria Collection. 1028824 records from SEAMAP - marine mammals, birds and turtles. 3 records from Japan Collection of Microorganisms, RIKEN BioResource Center. 3112 records from Ross A. Layberry, Collection. 1628 records from Entomology Department Collections, Natural History Museum of Denmark. 34 records from Vascular plants of south-central China. 36 records from UC Davis Department of Anthropology Museum. 33 records from Wiese und Weide am Waldrand von Gusterath. 305 records from Cuxhavener Küstenheiden. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 106 records from Occurrence of mammalia relicts at site Pod hradem. 430 records from Collection Strepsiptera SMF. 48242 records from Biological Records Centre - Millipede (Diplopoda) records for Britain and Ireland to 2005. 37 records from A brief review of Triplophysa (Cypriniformes: Balitoridae) species from the Tarim Basin in Xinjiang, China, with description of a new species.. 8328 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Diptera_Tipulidae_Palearctic. 63 records from (Table II) Abundance of epibenthic phyla and classes during RSS James Clark Ross cruise JR144. 6808 records from Hemiptera collection (EH) of the Muséum national d'Histoire naturelle (MNHN - Paris). 6011 records from Guadeloupe_Insectes. 8 records from A new species of the genus Nothobranchius (Cyprinodontiformes: Nothobranchiidae) from the coastal area of northeastern Mozambique.. 9 records from Kryptopterus platypogon, a new silurid catfish (Teleostei: Siluridae) from Borneo.. 577 records from Estación Experimental de Zonas Áridas (CSIC): EEZA-Herpet. 106100 records from Fish (NSMK-PI). 1 records from A new Camponotus from Madagascar and a small collection of ants from Mauritius.. 3 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 76300 records from KUBI Vertebrate Paleontology Collection. 25 records from Countryside Council for Wales - Freshwater Gwyniad Survey Data. 120 records from Birdrace_Steckbyer-Auenländler-Anhalt_Zerbst. 56 records from Streuobstwiese Haus Zeitz. 46 records from Unter hellen Zinnen und finsteren Grotten. 152 records from BIRDRACE NAJU-Aspach. 1 records from Living benthic foraminifera at station M33/1_MC-03 (NAST), size fraction 63-125 µm. 11431 records from Herp Specimens. 8 records from Herbario micológico de La Universidad de La Laguna, Tenerife: TFC_Mic. 613 records from Gastropoda, scaphopoda and amphineura abundance of surface sediments of the Atlantic continental shelf off Southern Spanish Sahara, West Africa (Table 2). 11 records from (Appendix B) Benthic foraminifera extinction group polpulation of ODP Site 202-1237. 1298 records from Colección de Aves y Mamíferos del Valle de Cuatrociénegas, Coah., México (UANL). 2 records from The Fungal Collection at the Botanische Staatssammlung München. 330 records from Macrobenthos in surface sediments off Sylt collected during Heincke cruise HE255. 117 records from Occurrence of ostracodes in ODP holes 101-627B and 101-635B (Table 1). 141 records from Echinoderms in surface sediments off Sylt collected during Heincke cruise HE206. 958 records from Sistemática y biogeografía del género Reithrodontomys (Rodentia: Muridae). 15705 records from Catálogo de insectos de la colección del Centro de Entomología. 788 records from Fauna de coleópteros lamelicornios del Estado de Michoacán (1995-2000). Primera Fase: Subprovincia neovolcánica tarasca (Cuenca del Lago de Pátzcuaro (1995-96). 4178 records from ARC- Plant Protection Research Institute, National Collection of Arachnida. 359262 records from VIS - Fishes in inland waters in Flanders, Belgium. 21172 records from Weddell Seal Sightings, Vestfold Hills, Antarctica. 3 records from Relative abundances of late Quaternary benthic foraminifera in ODP Site 90-594. 15 records from Artenvielfalt des "Grünen Klassenzimmers". 20 records from Vogelwelt im Europa-Rosarium. 34 records from Royal Botanic Garden Edinburgh Living Plant Collections (E). 490 records from EcoRecord - Mayfly (Ephemeroptera) records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 2 records from (Table 3) Distribution chart of dinoflagellate cysts and acritarchs from DSDP Hole 27-263. 7 records from Botanical Garden Collection. 5159 records from CNHE/Coleccion Nacional de Helmintos. 680 records from Schlern - (Bozen). 55 records from Überschwemmungsgebiet der Wied. 62 records from GEO-Hauptveranstaltung Bodden (Vilm). 25 records from Hemiodus jatuarana, a new species of Hemiodontidae from the rio Trombetas, Amazon Basin, Brazil (Teleostei, Characiformes).. 3 records from Arthropoden aus südostalpinen Höhlen.. 12 records from (Table 1) Trawled distance, Isopoda per 1000 m haul length, expected number of species, evenness, and the Shannon-Wiener index during POLARSTERN cruise ANT-XIX/4 (ANDEEP II). 139 records from Revision of the myrmicine ants of the Adelomyrmex genus-group (Hymenoptera: Formicidae).. 3 records from Trichomycterus giganteus (Siluriformes: Loricarioidea: Trichomycteridae): a new catfish from the Rio Guandu basin, southeastern Brazil.. 50 records from A survey of the family Carabodidae C. L. Koch, 1836 (Acari: Oribatida). 85 records from Countryside Council for Wales - Welsh Lesser Horseshoe Bat Summer Roost Surveillance Database. 109 records from Birdrace-Di_Bi_Di_Birder-Wesel. 94 records from Birdrace-Resopal_Altkreis_Dieburg-Team-Darmstadt/Dieburg. 23 records from AKG-Gelände in Bensheim. 2 records from LSG Saale, Rößewiesen (Bernburg/Saale). 2210 records from Merseyside BioBank - North Merseyside Mammals (unverified). 64 records from Ostracoda abundance of Hole 42-372. 76 records from Fish (MNHM-PI). 801 records from Collection Porifera - ZMB. 1023 records from Base de datos y la colección de eufáusidos (Euphausiacea: Malacostraca: Crustacea) del Atlántico mexicano. 69 records from Abundance of birds on the channels of Lena Delta in the brood period. 1 records from Plant (NHMK-PL). 10710 records from Birds (MNHM-BI). 156 records from SOVIET ANTARCTIC EXPEDITIONS for Zooplankton (R.V. OB March-May 1956, January-March 1957;R.V.ACADEMIC KURCHATOV, October 1971-January 1972; RV DMITRY MENDELEEV;R.V.ACADEMIC IOFFE 1992).. 48 records from Crustacea in surface sediments off Sylt collected during Heincke cruise HE275. 4566 records from Biological Records Centre - Ticks (Ixodidea) distribution for the British Isles. 2 records from Die Myriopodenfauna von Albanien und Jugoslavien. 1871 records from Registros biológicos de especies de fauna vertebrada terrestre en la central hidroeléctrica Miel I - 2009. 1500 records from Insect Specimens of Oiso Municipal Museum. 842 records from Marine specimens of Misaki Marine Biological Station, School of Science, University of Tokyo. 211 records from UAM Mammal Observations (Arctos). 3 records from Real Jardin Botanico, Madrid: MA-Musci. 32 records from The Deepwater Program: Northern Gulf of Mexico Continental Slope Habitat and Benthic Ecology - DgoMB: Invertebrates. 5291 records from Benthic biodiversity along the central coast in the Brazilian EEZ (OBIS South America, BRAZIL) (OBIS South America, BRAZIL). 468 records from BÜG. 384 records from Pilstingermoos. 32 records from Maschwiesen Laatzen. 135 records from http://www.geo-artenvielfalt.de (www.geo-artenvielfalt.de) - Birdrace-Pody&Co.-Plön. 120 records from Occurrence of mammalia relicts at site Jägerhaus-Höhle. 4 records from Herbier Ecole de Faune. 1 records from Herbarium of Namur. 10 records from University of British Columbia Herbarium (UBC) - Algae Collection. 71225 records from Vertebrate Paleontology Division, Yale Peabody Museum. 50688 records from Queensland Museum provider for OZCAM. 8760 records from Inventaire National du Patrimoine Naturel : Données Benthos du Réseau des Stations et Observatoires Marins. 1 records from Classification of the cribellate spiders and some allied families, with notes on the evolution of the suborder Araneomorpha. 65261 records from Mammals collection (ZM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 2858 records from Interactive Database of Biodiversity Studies on Terrestrial Arthropod Animals of Korea. 35018 records from Marine and Coastal Management - Demersal Surveys (years 2001-2005) (AfrOBIS). 11926 records from Crispin S. Guppy Collection. 9 records from USU-UTC Specimen Database. 2257 records from South Western Pacific Regional OBIS Data Asteroid Subset (South Western Paci fic OBIS). 1492 records from MfN Fish Collection, Zoology. 68768 records from CNIN/Lepidoptera. 134 records from Birdrace-Easy_Birders-Plön. 1 records from Occurrence of mammalia relicts at site Gladbeck. 175 records from Occurrence of mammalia relicts at site Weinberghöhlen/Mauern. 28 records from Hypostomus macushi, a new species of the Hypostomus cochliodon group (Siluriformes: Loricariidae) from Guyana.. 8000 records from Crustacean specimen detabase of Kanagawa Prefectural Museum of Natural History. 40 records from (Table 5) Record of mollusca and ostracoda fossils in sediments obtained from a dump area near Tessin. 13 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Especies observadas en Laguna Las Barrancas (Spitznagel, octubre 1999). 478 records from Royal Botanic Garden Edinburgh Herbarium (E). 353 records from Amphibia Collection of Museum and Institute of Zoology PAS. 7 records from On the centipedes (Chilopoda) of the Republic of Macedonia. 9 records from Rivulus uakti sp. n. and R. amanapira sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): two new species from the upper Rio Negro, Brazilian Amazon.. 1373 records from Finnish Entomological Database: Araneae. 3 records from On the centipedes (Chilopoda) of the Republic of Macedonia. 6 records from Taxonomic notes and distribution extension of Durga Das’s leaf-nosed bat Hipposideros durgadasi Khajuria, 1970 (Chiroptera: Hipposideridae) from south India. 1372 records from Northern Ireland Environment Agency - EHS Species Datasets. 459 records from Colección de Entomología - Coleoptera - Chrysomeloidea. 1667 records from EcoRecord - Mollusc records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 10 records from A new wobbegong shark, Orectolobus hutchinsi n. sp. (Orectolobiformes: Orectolobidae) from southwestern Australia.. 1 records from Egg capsules of Atlantoraja cyclophora (Regan, 1903) and A. platana (Günther, 1880) (Pisces, Elasmobranchii, Rajidae).. 1 records from On centipedes (Chilopoda) of Albania, 2. 28 records from RSPB - Black grouse lek survey in Moray and Nairn 2009 (RSPB). 18 records from (Table T3) Benthic foraminfera stratigraphy of ODP Hole 199-1221C sediments. 87310 records from Ouellet-Robert entomological collection (QMOR). 40 records from The identity of Pseudecheneis sulcata (M'Clelland, 1842), with descriptions of two new species of rheophilic catfish (Teleostei: Sisoridae) from Nepal and China.. 250 records from BATS & The Millennium Link - Bat records associated with the Union and Forth & Clyde canals (Period 2000 to 2005). 10926432 records from Tiira information service. 237 records from RSPB - Capercaillie national surveys (SCARABBS). 34 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña diciembre 2010. 2 records from Miscellaneous Vascular Plants. 132 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Fringillidae. 6754 records from Ichthyology. 819235 records from Bristol Regional Environmental Records Centre - BRERC October 2009. 31884 records from Naturalis Biodiversity Center (NL) - Amphibia and Reptilia. 6 records from Monomorium dentatum sp. n., a new ant species from Egypt (Hymenoptera: Formicidae) related to the fossulatum group.. 3530 records from Dorset Environmental Records Centre - Dorset SW Pilot species dataset. 442 records from Nematode abundance in sediments obtained during RRS Discovery cruise D297. 280 records from BIRDRACE Alb-Donaumoos-Kompetänzteam. 66 records from BIRDRACE Die schrägen Vögel aus dem Sauerland. 6 records from Distribution of meiobenthos in sediment core M23_203 of the northeastern Atlantic (Table 1). 20 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/363-1a. 8 records from Ostracoda abundance of Hole 42-375. 12607 records from Colección Ictiológica del Instituto Alexander von Humboldt. 9 records from Benthic macrofauna abundance of sediment core 13200-078. 29 records from Macrofauna biomass in surface sediment sampled during cruise DI229. 16 records from (Table 1) Diving behaviour of male Adélie penguins (Pygoscelis adeliae) with and without corticosterone implants at Pointe Géologie. 16 records from A review of the gobiid genus Akko (Teleostei: Gobiidae) with description of a new species.. 3 records from Seodaemun Museum of Natural History Mammal. 1 records from Tromsø Museum, Lichens. 8237 records from Naturalis National Natural History Museum (NL) – Pisces_Cichlidae of Lake Victoria. 32 records from Natural England - Species Surveillance Project - In-House Pilots records for 2012. 4251 records from Aves de la cuenca media del río Chambery, Caldas. 5772 records from UAFMC Fish. 9163 records from UAM Fish Collection (Arctos). 484177 records from Field Museum of Natural History (Zoology) Bird Collection. 800 records from PSUZC-Amphibians Collection. 15 records from (Table 3) Distribution of recurrent benthic foraminifera at DSDP Hole 75-530A, from Coniacian-Santonian to Albian. 18004 records from Census of the animals of Benin. 6 records from Dellwiger Bach (Dortmund). 51 records from Wassermann. 23 records from Park Schönfeld (Kassel). 10 records from schlittschuhweiher. 26 records from Schulteich Freie Waldorfschule Darmstadt. 2 records from Neues Testprojekt. 272 records from BIRDRACE Niederlausitz-Team. 101 records from BIRDRACE Enger am Spektiv. 107 records from BIRDRACE Borussia Zippammer. 18 records from Reusaer Wald. 17 records from Nachtinsekten am Muldenufer. 5841 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Coleoptera_Types_Orient. 1 records from Zwischen Enz und Schule. 11 records from Artenvielfalt und Kulturlandschaft. 460 records from MfN - Trace fossils. 280 records from Relative abundance of adult opstracoda shells of surface sediment samples from the Persian Gulf (Table 1b). 57 records from Macrofauna abundance in surface sediment sampled during cruise DI222/2. 51 records from Cartografía de vegetación a escala de detalle 1:10.000 de la masa forestal de Andalucía. 1368 records from Bird Collection of Yokosuka City Museum. 4996 records from Ohio State University Tetrapod Division - Amphibian Collection (OSUM). 28 records from Colección de Cocodrilos y Caimanes Museo de La Salle Bogotá (MLS). 11 records from A new rainbowfish (Teleostei: Melanotaenioidei: Bedotiidae) from the southeastern highlands of Madagascar, with comments on the biogeography of Bedotia.. 95 records from Birdrace-Buteo1_DO-Dortmund. 45 records from Ehmkendorf. 34 records from Naturgrundstück (Eutin). 24 records from Tag der Artenvielfalt BUND Kaiserslautern. 18 records from Artenvielfalt auf der Wiese. 79 records from Artenvielfalt im Schlosspark Sayn (Sayn/Bendorf). 14 records from Klütwald. 69 records from Bodenteicher Seewiesen. 29 records from Düpenauwiesen. 42448 records from Merseyside BioBank - North Merseyside Insects (unverified). 7 records from Abundance of nematoda in sediment profile M3/1_018 from the Iberian deep sea basin (Table 5). 3 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/321-1. 90 records from Binsenwiesen im Bizzenbachtal. 16 records from Physical properties, geochemistry and ostracoda abundance of sediment core Lz1080. 4 records from Benthic macrofauna abundance of sediment core 13077-087. 17619 records from Akita Prefectural Museum, Insect Collection. 4 records from Naturschwimmteich Casa Bianca. 16 records from A new fungus-growing ant genus, Mycetagroicus gen. nov. with the description of three new species and comments on the monophyly of the Attini (Hymenoptera: Formicidae).. 326 records from Elasmobranquios del sistema laguna Chantuto-Panzacola y Carretas-Pereyra de la Reserva de la Biósfera La Encrucijada, Chiapas. 2123 records from Diversidad de peces de las lagunas costeras de Pueblo Viejo y el Mango, Veracruz. 2000 records from Akita Prefectural Museum＋Obsevation records of Amphibians. 248680 records from Swiss National Orthoptera Databank. 9031 records from AIMS - LTM Nearshore Corals (OBIS Australia). 113933 records from TTU Mammals Collection. 1020 records from RMT Trawl catch from 1985/86 V1 ADBEX III voyage (Australian Antarctic Data Centre). 772 records from Sudeniederung (Amt Neuhaus), Landkreis Lüneburg. 2 records from Occurrence of mammalia relicts at site Endingen. 60 records from The genera of the Neotropical armored catfish subfamily Loricariinae (Siluriformes: Loricariidae): a practical key and synopsis.. 104 records from Birdrace-Diesmal_sehen_wir_mehr-Lippe. 81 records from Biosphäre Bliesgau. 20 records from Wiese Niederaula. 24 records from Kurler Busch (Scharnhorst). 60 records from Pollen and age analysis of terrestrial plant wax from ODP Hole 175-1085A. 110 records from BIRDRACE Angeliter Ornis. 146 records from BIRDRACE VdW Wilder Westen. 12 records from Ostracoda abundance of Hole 42-371. 10 records from (Table 1) Early Miocene and late Oligocene ostracods in sediment core CRP-2A. 33 records from Meiofauna abundance in sediment core 12930-007. 101 records from Benthic macrofauna abundance of subcores of sediment core 13078-015. 43 records from Antarctic and sub-Antarctic Lophogastrida occurrences. 1825 records from The Paleontological Collections at the Bayerische Staatssammlung für Paläontologie und Geologie. 3559 records from Actualización de bases de datos de peces. 1505 records from Inventario de los mamíferos de las reservas de la biósfera Mapimí, La Michilía, El Cielo y Calakmul. 1648 records from WAHerb. 28 records from The Provincial Museum of Newfoundland and Labrador Natural History Collection. 126759 records from Fish specimens. 1256 records from Isle of Wight Local Records Centre - IOW Natural History & Archaeological Society Marine Invertebrate Records 1853- 2011. 17 records from Occurrence of mammalia relicts at site Bivak Cave. 1 records from Occurrence of mammalia relicts at site Ejstrup. 30 records from Occurrence of mammalia relicts at site Jaskinia Niedwiedzia. 31 records from Gymnicher Mühle. 8418 records from HSU Wildlife Birds. 2 records from Zur Oribatidenfauna des Leopoldsberges von Wien (1. Beitrag). 129 records from Succession of benthic hard-bottom communities abundance at station Errina2012_AG. 956 records from Coleoptera of Tuchola Forest and Tuchola Forest National Park. 5 records from (Table 4) Composition of turbidite and background samples at ODP Site 166-1007. 1 records from Arthropoden aus südostalpinen Höhlen.. 2596 records from Collection Ornithologie - ZSRO. 12 records from (Table 2) Occurrence of Oligocene to Pleistocene benthic foraminifers in ODP Site 121-756. 65066 records from Formación de una base de datos y elaboración de un atlas de la herpetofauna de México. 1092 records from Caracterización y estructura de la ictiofauna de arrecifes rocosos y coralinos en Punta Carrizal, Colima, México para fines de inventario y conservación de la diversidad animal. 14821 records from Parasitic Platyhelminthes Collections. 39784 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 2001) (AfrOBIS). 54059 records from Pelagic Fish Observations 1968-1999. 25 records from Wiese und Bach am Kleinen Eutiner See (Eutin). 48 records from Umgebung der Elsa-Brändström-Schule (Krückaupark). 172 records from Kühnauer See (Dessau). 6 records from Occurrence of mammalia relicts at site Upton Warren. 52 records from Occurrence of mammalia relicts at site l´Abri du Morin. 581 records from Studies in Hawaiian Diptera II: New Distributional Records for Endemic Scatella (Ephydridae). 12945 records from CUMV Reptile Collection (Arctos). 72554 records from Insect Collection of Taiwan Forestry Research Institute. 25 records from Lethrinus ravus, a new species of emperor fish (Perciformes: Lethrinidae) from the western Pacific and eastern Indian oceans.. 71 records from Occurrence data of Ectyphus and Parectyphus (Diptera: Asiloidea: Mydidae). 5 records from Specimen records associated with "A troglomorphic spider from Java (Araneae, Ctenidae, Amauropelma). 11 records from Six new species of the spider family Ochyroceratidae Fage 1912 (Arachnida: Araneae) from Southeast Asia. 114 records from Birdrace-Finkenspötter-München. 98 records from Birdrace-Die_Nachtraben-Stuttgart. 47 records from Schulgarten Hans-Carossa-Oberschule. 149 records from Birdrace-Usedommeln-Ostvorpommern. 28 records from Schulgelände Freiherr-vom-Stein-Gymnasium (Hamm). 139 records from Bannwald Burghauser Forst. 100 records from BIRDRACE Lohmanns Öömi-Studenten. 396 records from Colección de Entomología - Auchenorrhyncha. 7297 records from University of Ghent - Zoology Museum - Invertebratacollectie. 15382 records from Bird Specimens in the Museum of Nature and Human Activities, Hyogo, Japan. 53 records from Squid collection from 1995/96 V4 BROKE. 45 records from Pliocene/Pleistocene benthic foraminiferal abundances from hole KR9912PC4. 16201 records from Iberian Odonata distribution: data of the BOS Arthropod Collection (Univ. Oviedo, Spain). 43 records from Pollen profile I at Krumbach. 1 records from Fundación Carl Faust: Herbario del Jardí Botànic Marimurtra: HMIM. 7 records from (Table 2) Plio-Pleistocene benthic foraminifera of ODP Hole 107-654A. 10 records from A new Neoplatyura Malloch from Finland (Diptera, Keroplatidae). 4540 records from Inventario de la mastofauna en las reservas de la biosfera Desierto del Vizcaíno y Valle de los Cirios. 1360 records from Contribución a la riqueza ictiofaunística de la Reserva de Ría Lagartos, Yucatán. 29128 records from Diversidad bentónica del ambiente intermareal e infralitoral somero de Progreso, Yucatán. 3 records from Akita Prefectural Museum＋Sentipedes Specimens of Akita Prefectural Museum. 27300 records from Natural Geography In Shore Areas (NaGISA) Dataset. 29877 records from Canadian Museum of Nature - Fish Collection (OBIS Canada). 1023 records from Spencer Entomological Museum. 3846 records from University of Alberta Museums, Freshwater Invertebrate Collection. 11 records from HBGBryophyta - Herbarium Hamburgense. 41695 records from AIMS LTM Fish (OBIS Australia). 28934 records from Coleção de Abelhas do Museu de Ciências e Tecnologia da PUCRS. 4 records from Pycnogonida collection of National Museum of Nature and Science. 263 records from Naturschutzgebiet Sistig-Krekeler-Heide. 41 records from Alte Ziegelei, Lehmgrube (Mainz-Bretzenheim). 121 records from renaturierter Main (Kemmern bei Bamberg). 13 records from Occurrence of mammalia relicts at site Biedensteg. 51 records from Occurrence of mammalia relicts at site Moladova V. 42 records from Occurrence of mammalia relicts at site l´Abri de Rhodes II. 50 records from Occurrence of mammalia relicts at site Goyet Cave 3. 8 records from Occurrence of mammalia relicts at site Grotte du Prince. 12 records from Steinbruch Mainz-Weisenau, 4.Jahr. 1449 records from Abundance of the benthic infauna of the North Sea sampled during Victor Hensen cruise VH1486. 74164 records from Marine and Coastal Management - Linefish Dataset (First Semester of 2000) (AfrOBIS). 14763 records from Herp Collection. 323 records from CNAN/Pseudoscorpiones. 7 records from Herbarium de Geo. B. Hinton, México. 77 records from Naturschutzgebiet Heiliger Hain (Wahrenholz). 1801 records from Vertebrate specimens of Jyväskylä University Museum. 3 records from Abundance of benthos infauna at station GIK23006-3. 51499 records from NRM-Fishes. 14549 records from Alterra (NL) - Comparison of entomofauna in four different habitats. 743 records from Fish monitoring data in Lake Kasumigaura. 370 records from Collection Crustacea - KAUMM. 13 records from Schulhof Sandhofenschule (Mannheim). 36 records from Biotop Binsenwiesen und Ernst-Reiter-Wiese (Wehrheim/Taunus). 58 records from Waldfläche im Natur-Erlebnis-Pfad Pfinztal. 4 records from Absolute abundance of particles and planktic foraminifera in sediment core GIK12310-4, Cape Barbas, North-West Africa (Appendix Tab. 2c). 115 records from Bayerische Donau - Blindheim Donaubrücke. 75 records from (Table 2) Ostracode assemblages and environment characteristica of modern surface sediment samples from Patagonia, Argentina. 14 records from A review of the genus Mystrium (Hymenoptera: Formicidae) in the Indo-Australian region.. 127 records from BIRDRACE Southernmost Lakers. 54 records from Collection Cnidaria - ZIM Hamburg. 288 records from Gorgonacea specimens of Kuroshio Biological Research Foundation. 501592 records from Western Australian Museum provider for OZCAM. 6 records from Molluscs in surface sediments off Sylt collected during Heincke cruise HE293. 5727 records from Propuesta para rescatar y conservar la paleobiota de la Cantera Tlayúa, en Tepexí de Rodríguez, Puebla: Fase II. 871 records from GEO-Hauptveranstaltung (Insel Vilm). 107 records from Weinberge und angrenzende Felsflächen (Drieschen) in Hatzenport/Terrassenmosel. 29362 records from Highland Biological Recording Group - HBRG Vertebrates (not Badger) Dataset. 1 records from Nothrus farinosus. 20 records from Review of the Camponotus aureopilus species-group (Hymenoptera, Formicidae), including a second Camponotus with a metapleural gland.. 1 records from Benthic foraminifera abundance of Hole 34-320A. 197 records from Type Localities for organisms and fossils first described from Antarctica. 12 records from Mean abundance Ophiocten gracilis and sediment surface area covered by the ophiuroids according to total diameter of individuals at different stations on Vøring Plateau. 1733 records from Naturalis National Natural History Museum (NL) – Acari_Types. 67371 records from Swedish Board of Fisheries (Fiskeriverket) - Swedish Electrofishing Registry. 324 records from Alterra (NL) - Microarthropods inventory in Heathland. 21 records from Two new species of Brueelia Kéler, 1936 (Ischnocera, Philopteridae) parasitic on Neotropical trogons (Aves, Trogoniformes). 205 records from Fortalecimiento de los procesos de recuperación natural y cultural en la Sierra Nevada de Santa Marta. 1 records from On two italian Lithobius species described by Silvestri with taxonomic notes on the genus Eupolybothrus Verhoeff (Chilopoda Lithobiidae). 8 records from Pollen profile from sediment core AV14_K2-2. 13 records from Environment Agency - Environment Agency white-clawed crayfish Survey of the River Lune Catchment 2004. 63 records from Museu Paraense Emilio Goeldi - Ricinulei Collection. 235 records from Pseudoscorpions of Ireland. 766 records from Reptiles and Amphibians Distribution Atlas 1978 (An Foras Forbartha). 4 records from Four new species of deep-water catsharks of the genus Parmaturus (Carcharhiniformes: Scyliorhinidae) from New Caledonia, Indonesia and Australia.. 14852 records from VERTEBRADOS DE VALOR ESPECIAL EN ÁREAS PROTEGIDAS DE LA ARGENTINA. 2 records from Parvimyrma gen. nov. belonging to the Solenopsis genus group Hymenoptera: Formicidae: Myrmicinae: Solenopsidini).. 12 records from (Table IV) Abundance of isopoda families during RSS James Clark Ross cruise JR144. 32624 records from Paleontological collection of the National Museum - Fauna. 106920 records from Naturalis Biodiversity Center (NL) - Lepidoptera. 1 records from The millipede Typhloglomeris caucasica Golovatch, 1975 found epigeically (Diplopoda, Glomerida, Glomeridellidae). 24 records from A revision of the Indo-Pacific fish genus Caragobius (Gobiidae: Amblyopinae).. 60491 records from QLD DERM Coastal Bird Atlas (Trial). 139 records from BIRDRACE Turbine Untersee. 30 records from Hydroids of the BANZARE Antarctic expeditions 1929 - 1931. 18 records from Composition of benthic macrofauna in surface sediments of the east Greenland continental slope (79° N section). 16866 records from Gravel Master Thesis / Chubut, Argentina. 4 records from Arthropoden aus südostalpinen Höhlen.. 4 records from Simpsonichthys nielseni sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual killifish from the São Francisco River basin, Brazil.. 92137 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 74 records from Registros biológicos del Humedal Santa Maria del Lago 1999-2013. 2090 records from Crustáceos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CERBMcr-UV). 3 records from On two Italian Lithobius species described by Silvestri, with taxonomic notes on the genus Eupolybothrus Verhoeff (Chilopoda, Lithobiida). 4 records from Pollen analysis of sediment profile PLU01 from Plussee. 408749 records from Joint Nature Conservation Committee - Marine Nature Conservation Review (MNCR) and associated benthic marine data held and managed by JNCC. 1390 records from Caracterización de avifauna de la subcuenca del Río San Pedro, San Pedro, Valle del Cauca. 31273 records from SABCA. 100 records from Beweidungsprojekt an der Nesse. 36 records from Stever. 27 records from GymnQuerfurt. 41 records from Mainufer. 128 records from Birdrace_turbine_untersee-Konstanz. 5 records from Streuobstwiese. 114 records from BIRDRACE LiLaLau. 29 records from Schulgarten Zinnowwald-GS. 4 records from Distribution of meiobenthos in sediment core M23_123 of the northeastern Atlantic (Table 1). 57 records from Royal penguin Eudyptes schlegeli census, Macquarie Island, 1984. 28 records from Matter enrichment of the macrofauna community of MAC station 13368-008. 8 records from Little known Orphninae (Coleoptera, Scarabaeidae) collected by the Madagascan expeditions of the California Academy of Sciences. 370 records from Lichen herbarium, Oslo (O). 1724 records from Saproxylic Beetles of the Tatra Mts.. 61717 records from South East Wales Biodiversity Records Centre - Microlepidoptera of Glamorgan . 101 records from MVZ Mammal Observations (Arctos). 230991 records from MVZ Mammal Collection (Arctos). 24 records from (Table 1) Stage of the lemming cycle and nesting parameters of the greater snow geese between 1996-2005, Bylot Island. 639105 records from Norwegian Biodiversity Information Centre - Other datasets. 78649 records from Recent Invertebrates Specimens. 110 records from Birdrace-LiLaMai-Vechta. 17 records from Örtzemündung (Stedden). 39 records from Dorfrand Mauderode. 85 records from Birdrace-Halsbandschnäpper-Stuttgart. 71442 records from All Ireland Non-Marine Molluscan Database. 7115 records from Microlepidoptera, National Museum of Ireland. 40 records from Pollen profile from Seminary School Basin. 117 records from Eschlberg Thalhausen. 4760 records from SO-Polylist. 1 records from The Exsiccatal Series "Triebel, Microfungi exsiccati". 11981 records from SMNK Mantid Collection. 67109 records from Ehime University Coleoptera Collection. 4 records from Neolamprologus devosi sp. n., a new riverine lamprologine cichlid (Teleostei, Cichlidae) from the lower Malagarasi River, Tanzania.. 26 records from Water Colours of Fungi by Fritz Wohlfarth at the Botanische Staatssammlung München. 189 records from Fish larvae biodiversity along the central coast in the Brazilian EEZ (OBIS South America, BRAZIL) (OBIS South America, BRAZIL). 1 records from Plant specimens depodited in Osaka Museum of Natural History, Japan.. 547 records from RMT Trawl catch from the 2005/06 V3 BROKE-West voyage - Fish. 64 records from Tiergarten Straubing. 195 records from Walldorf-Wiesloch: "Natur über den Gleisen". 55 records from Occurrence of mammalia relicts at site l´Abri des Battuts I. 1051 records from University Marine Biological Station Millport - 1999-2009 UMBSM Clyde Sea Fairlie Channel Beam Trawl Survey. 13 records from Oberservation of birds at station PS14/159 along 49° West. 8 records from Revision of the ant genus Anillomyrma Emery, 1913 (Hymenoptera: Formicidae: Myrmicinae: Solenopsidini).. 23 records from Succession of benthic hard-bottom communities abundance at station Errina2012_CS. 51390 records from Scottish Wildlife Trust - The Scottish Squirrel Database. 1578 records from Palaeobiology collection, FAU Erlangen. 1212397 records from Fishbase. 1 records from Zetes ephippiatus. 4308 records from Marine Biological Association - Volunteer sightings data held by the DASSH Data Archive Centre. 9 records from The Oribatid Family Phthiracaridae II. Redescription of Phthiracarus laevigatus (C. L. KOCH). 165365 records from KUBI Mammalogy Collection. 75 records from Empria and Monsoma in Japan. 231 records from (Table 1) Fossil record of foraminifera and ostracoda from Albersdorf clay pit, north Germany. 60 records from (Appendix A) Palynofacies raw counts of DSDP Hole 38-338. 303 records from Ichthyologie ZMK. 31 records from RSPB - Spotted crake national survey in the UK in 1999 (SCARABBS). 37 records from Neanderthal. 40 records from Aachtobel. 37 records from Was lebt in der Brutzwiese?. 7 records from Kindervilla Außengelände. 253 records from Mosquitoes (Diptera: Culicidae) of Ireland. 18166 records from Museu de Ciències Naturals de Barcelona: MCNB-Cord. 46839 records from Saltabel - Orthoptera in Belgium. 12 records from TBW-Schafberg. 138 records from RMT Trawl catch from the 1983/84 V5 ADBEX II voyage. 7 records from Appendicularia abundance of station M9_C near the Great Meteor Bank, Northeast Atlantic (Table 2). 37 records from Palynological analysis of sediment core GeoB3910-2. 85 records from Fig 14. Pollen profile from sediment core Schmiecher See. 181600 records from Macaulay Library Audio and Video Collection. 766 records from Biodiversidad acuática del río Amacuzac, Morelos, México. Peces. 940 records from Mastofauna de la vertiente occidental (oeste) del Parque Nacional Pico de Orizaba, Puebla (Fase 1). 2 records from Akita Prefectural Museum＋Specimens of Class Pycnogonida of Akita Prefectural Museum. 17 records from Wälder im Hainbachtal. 20841 records from Museu Paraense Emilio Goeldi - Ornithology Collection. 4 records from (Table 1) Occurrences of ostracodes in ODP Hole 122-761B. 4728 records from Incorporación de nuevos registros de mamíferos de la región Sierra Norte de Oaxaca. 761 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during Walther Herwig cruise WH220. 32649 records from mammals. 48394 records from Bird specimens. 1795 records from Galathea II, Danish Deep Sea Expedition 1950-52. 364 records from Bird tissues, Division of Genomic Resources, UNM, Albuquerque, NM.. 29874 records from European Moth Nights. 2 records from Acari fossil - SMNG. 574 records from Gesamtartenliste Bremerhaven, Helgoland und Sylt. 216 records from Occurrence of mammalia relicts at site Pestera Cioarei. 53 records from Occurrence of mammalia relicts at site Tornewton Cave. 34 records from Occurrence of mammalia relicts at site Villa Seckendorff. 90 records from Occurrence of mammalia relicts at site Felsställe. 945 records from Amphibian and Reptile Conservation - NARRS Data 2007 - 2011. 2318 records from Fundación Miguel Lillo - Colección Ictiológica. 4 records from Pachycondyla nigrita and related species in Southeast Asia.. 3 records from New data of three rare belondirid species (Nematoda, Dorylaimida, Belondiridae) from Vietnam, with the first record and description of the male of Oxybelondira paraperplexa Ahmad & Jairajpuri, 1979. 2880 records from Coleoptera, NEF. 26799 records from Bird Monitoring Data. 4268 records from Free-living marine Nematodes from Ali, Rada Tilly and El Limite sandy beaches (Chubut, Argentina) 2006.. 6 records from Wedeler Au. 74 records from Gewässer des Wartbergparks Stuttgart (beim Naturlabor der Umweltakademie Baden-Württemberg). 40 records from Öhmdwiesen und Göldern (Konstanz). 26 records from "Ahrschleife bei Altenahr". 4 records from Benthic macrofauna abundance of sediment core 13200-025. 2598 records from Insecta ZMK. 8334 records from Birds (GMBO-BI). 26 records from The Vascular Plant Collection at the Botanische Staatssammlung München. 181 records from Table I: Birds observed at the Weddell Sea during the period: 6 December 1955 to 19 January 1956. 130 records from BIRDRACE - The famous Grouse feat. The James. 1056 records from Range chart for Tertiary ostracodes from ODP Hole 101-628A (Table 1). 1 records from Die Myriopodenfauna von Albanien und Jugoslavien. 189 records from (Table 16) Distribution of ostracode species in Core PS51/080-13. 2 records from Pollen record of profile 2TZ2. 3472 records from Cnidarios, poliquetos, crustáceos (decápodos) y quetognatos pelágicos del Golfo de California. 678 records from Ictiofauna de los ríos Papagayo, Atoyac y Coyuca. 8593 records from Inventario de la biodiversidad de vertebrados terrestres de los Chimalapas, Oaxaca. 108312 records from Ornithology Collection Passeriformes - Royal Ontario Museum. 876 records from Posidonia Oceanica Survey 2005 (EurOBIS). 26473 records from MSUM Ichthyology and Herpetology Collections. 1 records from University of Copenhagen Arboretum. 81037 records from Museum of Zoology, University of Navarra. 13195 records from Fish Collection of Natural History Museum and Institute, Chiba. 767 records from RAVON (NL) - Fish observations extracted from Hoek (1890) and Redeke (1921). 13225 records from Colección de Mamíferos del Museo de Zoología 'Alfonso L . Herrera', México (MZFC, UNAM). 78 records from Schule Sulzbach (Oberegg). 31 records from Wiese am Waldrand (Gurtweil). 103 records from NABU-Projekt (Osterode am Harz) Südharzer Gipskarst. 68 records from Schussenaue (Weingarten). 67725 records from Patterns of widespread decline in North American bumble bees. 14 records from Occurrence of mammalia relicts at site Bettenroder Berg IX. 79 records from RSPB - Black grouse lek survey in Sutherland 2008-9 (RSPB). 89 records from NSG Haunestausee, Hauneteiche. 202194 records from Tulane University Museum of Natural History. 133 records from Bryophyte Collection - University of Washington Herbarium (WTU). 7 records from Vascular Herbarium, NMBU. 51707 records from EcoRecord - Bird records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 18920 records from The Arthropoda Varia Collection at the Zoologische Staatssammlung München. 2467 records from Coleccion Herpetologica Reptiles LJAMM-CNP. 15455 records from Laboratorio de Entomología y Control de Plagas del Instituto Cavanilles de Biodiversidad y Biología Evolutiva de la Universidad de Valencia: ENV. 342 records from The Deepwater Program: Northern Gulf of Mexico Continental Slope Habitat and Benthic Ecology - DgoMB: Fish. 87678 records from Herp specimens. 607597 records from Paleobiology Database. 19062 records from Mammal specimens. 1 records from Nordic Genetic Resources. 1498 records from Marine invertabrate(ARTHROPODA) specimen database of Osaka Museum of Natural History. 18 records from Schulumgebung Grüterschule, Rheine. 43 records from Renaturierung Werse (Innenbereich Beckum). 11 records from Occurrence of mammalia relicts at site Gröbern. 30 records from Occurrence of mammalia relicts at site la Grotte des Eglises. 114074 records from UTA Herpetology. 11 records from Spider hosts (Arachnida, Araneae) and wasp parasitoids (Insecta, Hymenoptera, Ichneumonidae, Ephialtini) matched using DNA barcodes. 236 records from Mosses (S). 118309 records from Therevid PEET Project. 440 records from CNMA/Colección de Mamíferos de la Estación de Biología Los Tuxtlas. 1 records from Abundance of benthos infauna at station GIK23013-2. 7 records from University of Ghana - Ghana Herbarium. 1740 records from Monitoring data from the federal state Berlin (Germany). 6 records from Una nuova specie di Eupolybothrus della fauna di Grecia (Chilopoda, Lithobiomorpha). 5195 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Diptera_Types. 15 records from A survey of the family Carabodidae C. L. Koch, 1836 (Acari: Oribatida), II. 216081 records from Fieldjournal.org observation database. 8069 records from University of Ghana - Ghana Herbarium, Insects collection. 417 records from BoBO - Botanic Garden and Botanical Museum Berlin-Dahlem Observations. 1500 records from Amphibian and Reptilian (ENHM-AR). 48 records from (Figure 11) Distribution of Cretaceous planktonic foraminifers and associated organisms from DSDP Hole 77-538A. 531188 records from MVZ Herp Collection (Arctos). 17998 records from Molluscan specimen database of Kanagawa Prefectural Museum of Natural History. 1432 records from Barrow Island Ants. 12 records from The African species of the subfamily Penestominae (Araneae: Eresidae): with descriptions of two new species. 1 records from Oppia nitens. 1225403 records from AntWeb. 5 records from A new species and records of Diolenius Thorell, 1870 (Araneae: Salticidae) from New Guinea. 233 records from Dataset for Review of Mimosticus Sharp (Coleoptera: Staphylinidae). 7458 records from Colección de Reptiles del Instituto Alexander von Humboldt. 10 records from Mittelriede Höhe Gliesmarode-Braunschweig. 5 records from Distribution of meiobenthos in sediment core M19_202-2 of the northeastern Atlantic (Table 1). 19 records from Schulhof (Bad Waldsee). 187 records from Artenfülle um das Schalkenmehrener Maar. 332 records from Freigelände Naturschutzscheune Reinheimer Teich (Kreis Darmstadt-Dieburg). 4 records from (Table 1) Distribution of benthic foraminifers at DSDP Site 90-590. 8 records from A new glanapterygine catfish of the genus Listrura (Siluriformes: Trichomycteridae) from the southeastern Brazilian coastal plains.. 6663 records from Biological Records Centre - Pseudoscorpion Recording Scheme of the UK. 58029 records from Colección nacional de zoología. 396 records from RSPB - 2008 Farmland Bird Survey North East Wales - RSPB/CCW. 59498 records from Leicestershire and Rutland Environmental Records Centre - Leicestershire & Rutland Coleoptera. 23046 records from Hemipteran specimens of Iwate Prefectural Museum. 90 records from Steinbruch Mainz-Weisenau, 2. Jahr. 33 records from Feuchtbiotop, Wildtier- und Artenschutzstation Sachsenhagen, Sielmanns Natur-Ranger. 25 records from Wiese hinter der Schule (Darmstadt). 3 records from (Table 7) Absolute abundances of benthic foraminifera in Neogene sediments of DSDP Site 90-588_Site in the southwest Pacific. 189599 records from The Distribution Atlas of Butterflies in Poland. 91 records from (Table 2) Ostracoda abundances in sediment core PS2185-6 (Lomonosov Ridge). 230 records from A taxonomic revision of the Neotropical myrmicine ant genus Lachnomyrmex Wheeler (Hymenoptera: Formicidae). 1 records from A new species of Asphinctopone (Hymenoptera: Formicidae: Ponerinae) from Tanzania.. 133 records from Description of Haploblepharus kistnasamyi, a new catshark (Chondrichthyes: Scyliorhinidae) from South Africa.. 227 records from Colección de Salamandras Museo de La Salle Bogotá (MLS). 14 records from Census of the flora of Benin. 111503 records from Highland Biological Recording Group - HBRG Insects Dataset. 198 records from Segunda caracterización biológica de hormigas cazadoras del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 26925 records from Colección de Aves de Colombia del Instituto Alexander von Humboldt. 7 records from Kryptolebias sepia n. sp. (Actinopterygii: Cyprinodontiformes: Rivulidae), a new killifish from the Tapanahony River drainage in southeast Surinam.. 9285 records from UK Cetacean Strandings Investigation Programme - Stranded cetacean data from Great Britain collected from 01/01/89 through to 31/03/10. 27 records from Kinder- und Jugendferiendorf des Kreises Groß-Gerau - Gedern/Ober-Seemen. 50 records from Panke und Ufer am Kinderbauernhof Pinke-Panke. 92 records from Schulgelände Paul-Gerhardt-Schule-Dassel. 39 records from Stausee Weiditz. 69 records from BIRDRACE Pfeifenten. 91 records from BIRDRACE NABU LV Hessen. 102 records from Naturschutzgebiet Börstig bei Hallstadt. 53 records from BIRDRACE Taubenhaucher. 23 records from Leben auf einer Sturmfläche. 321020 records from Biodiversity Institute of Ontario (BIOUG). 61 records from Coleoptera identified from the St. Paul's Academy site, Abbey Wood, London. 10 records from BB-Biodiversität b. 50 records from Pfingstexkursion Alter Bessin. 153 records from annex1. 30189 records from Environment Agency - Environment Agency Non-native Species records v1. 14017 records from Museu de Ciències Naturals de Barcelona: MCNB-Art. 5538 records from Colección Alberto Tinaut (Formicidae). 1636 records from Fish (ASJK-PI). 103455 records from ANTAVIA-TrackingKing. 8 records from Landwehrbach. 86648 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1991) (AfrOBIS). 213 records from Dr Francis Rose Field Notebook Project - Field Notebook Records of Dr Francis Rose 1950's to 1990's. 130059 records from Inventaire National du Patrimoine Naturel : Mammifères de France. 6083 records from Biological Records Centre - Sepsidae (Diptera) records from Britain and Ireland to 1985. 28267 records from UAM Bird Collection (Arctos). 9948 records from Bees of Canada / Gschwendtner property collection. 4873 records from Berkshire Reptile and Amphibian Group - BRAG - Berkshire Reptile and Amphibian Records . 163 records from Entomofauna laguna El Tinije. 103 records from Birdrace-Borussia_Zippammer-Bad Kreuznach. 40 records from Westerwälder Umwelt- und Naturschutztag Limesgemeinde Hillscheid. 37 records from Grillhütte Wettsaasen, Wiese, Hecken. 167 records from Birdrace-Cuxland_Schwenke_GeoConsult-Cuxhaven. 35 records from EcoRecord - Fungi & Lichen records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 27 records from Sternwiese Mülheim-Broich. 21 records from Tauchen und Meer. 3 records from Blankenfelder See. 118 records from BIRDRACE Die Lippegeier. 102 records from http://www.geo-artenvielfalt.de (www.geo-artenvielfalt.de) - BIRDRACE *Bkassine*. 13 records from Liether Park 1 (LMS), Klasse 5b. 210 records from RSPB - Black grouse lek survey in the Scottish Borders, 2010 (Southern Upland Partnership). 81 records from Dornwanger Moos. 26 records from Werl macht sich auf die Suche. 43 records from MfN - Fossil plants (Paleophytic). 21 records from Ostracoda abundance of Hole 24-237. 85 records from RSPB - Black grouse lek survey in Ross-shire. 1250 records from Colección de Crustáceos Macrobénticos del Golfo de México (ICMyL-DF, UNAM). 53062 records from British Antarctic Survey Argos satellite tracking data. 6680 records from SOMBASE PYCNOGONIDS. 409 records from Macrobenthos in surface sediments off Sylt collected during Heincke cruise HE272. 23 records from Palynology of profile Füramoos III. 3422 records from Distribución y aspectos taxonómicos de los corales pétreos (Anthozoa: Scleractinia) del Pacífico mexicano. 362 records from Centre d'Estudis Avançats de Blanes, Macroinvertebrados Limno. 7 records from Collection Hemiptera - SNSD. 73544 records from Marsh Monitoring Program - Birds. 3 records from Botanical Museum, Copenhagen. Database of type specimens. 35 records from (UTCFB) University of Tennessee - Fossil Birds Collection. 1698 records from RSPB - Red-throated diver national surveys in Scotland - raw data (SCARABBS). 16620 records from Crustacea collection of National Museum of Nature and Science. 78 records from Birdrace-Die_Laufenten-Braunschweig. 5 records from Streuobstwiesengebiet (Kreis Ahrweiler). 66 records from BIRDRACE Die schrägen Vögel aus dem Sauerland 2. 5 records from Distribution of meiobenthos in sediment core M19_197-2 of the northeastern Atlantic (Table 1). 41 records from MfN - Fossil invertebrates Ib. 6 records from Benthic macrofauna abundance of sediment core 12930-093. 100 records from Benthic macrofauna abundance of subcores of sediment core 12930-084. 143 records from BIRDRACE Punkbirder Helgoland. 162 records from Antarctic fish Gobionotothen gibberifrons. 90 records from Polychaetes in surface sediments off Sylt collected during Heincke cruise HE218. 11 records from Appendicularia abundance of station M9_A near the Great Meteor Bank, Northeast Atlantic (Table 1). 4 records from Base de datos sobre la flora de Durango. 581051 records from Swiss National Butterflies Databank. 292 records from Atlantic Forestry Centre Insect Reference Collection. 24268 records from Ross A. Layberry Observations. 11027 records from Hymenopteran specimen database of Osaka Museum of Natural History. 566 records from Marine Benthic Fauna List, Island of Læsø, Denmark. 522 records from (UTCFM) University of Tennessee - Fossil Mammals Collection. 13111 records from Herp Collection. 104 records from Tag der Artenvielfalt in der Stadt Luzern. 132 records from Benthic meiofauna abundance in surface sediment of core PLG93_BCORE3. 70 records from Instituto Nacional de Pesquisas da Amazônia - Porifera Collection. 5920 records from Alterra (NL) - Microarthropods inventories by Henk Siepel on various locations. 993 records from Rossendale Ornithologists' Club - ROC RSPB Farmland Species Survey Dataset. 4098 records from Anthomyiidae Study Group - Anthomyiidae records for Great Britain. 170897 records from Reptiles and Amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 1897 records from Shellfish (WSHN-MS). 5913 records from An Atlas of Breeding Birds of the Burren and Aran Islands 1993 - 1996. 15 records from Klassenfahrt Usedom / Wald und Küste in Zinnowitz. 17 records from Molluscs in surface sediments off Sylt collected during Heincke cruise HE206. 40 records from Palynology of profile Füramoos. 180 records from Biodiversidad acuática del río Amacuzac, Morelos, México. Anfibios. 1 records from Zetes semirufus. 3538 records from Anfibios del Estado de Veracruz.. 737 records from Biodiversidad de Veracruz: Oligochaeta. Annelida. 3045 records from Obtención de la riqueza de aves y selección de especies susceptibles de monitoreo en la zona noroeste en el estado de Chiapas. 1636 records from Ibaraki Nature Museum, Birds collection. 49 records from The Deepwater Program: Northern Gulf of Mexico Continental Slope Habitat and Benthic Ecology - DgoMB: Amphipods. 48566 records from North West Territories and Nunavut Bird Checklist, Canada. 45009 records from California Beetle Project. 1170 records from Colección de Cnidarios. 188 records from CNAN/Tipos Arachnida. 17152 records from Aves MZS. 246 records from Rotifers of Macquarie Island. 62 records from Bergbaufolgelandschaft am Muldestausee. 135 records from Scottish Natural Heritage - Site Condition Monitoring Records from surveys of lamprey species in five river SACs in Scotland . 2 records from Rivulus kayapo n. sp. (Teleostei: Cyprinodontiformes: Rivulidae): a new killifish from the serra dos Caiapós, upper rio Araguaia basin, Brazil.. 34 records from Occurrence of mammalia relicts at site Erdhöhle. 78 records from Rössewiesen am Krumbholz. 22 records from Wildgehege Glauer Tal (Naturpark Nuthe-Nieplitz). 1742 records from SCID Database. 52955 records from Collection Arachnology SMF. 463 records from UAM Herpetology Collection (Arctos). 144 records from Taxonomy of the South American genus Pachypops Gill 1861 (Teleostei: Perciformes: Sciaenidae), with the description of a new species.. 10 records from ENDEMIC SPECIES RESEARCH INSTITUTE（Herbarium）. 6330 records from Colección de Referencia de Coleópteros Mexicanos (IE-XAL). 48 records from Pollen counts of sediment core GeoB9503-5. 175 records from (Enclosure 1, Fig. 1) Complete pollen spectra of the samples represented by the composite pollen diagram from site Samerberg. 307 records from Diversidad y distribución de las comunidades de peces de ríos y lagunas del volcán San Martín de la reserva de la biósfera Los Tuxtlas. 23417 records from Korea Bird Distribution Atlas Database. 2 records from The AAU Herbarium Database. 579 records from Nova Scotia Museum of Natural History - Marine Birds, Mammals, and Fishes (OBIS Canada). 35693 records from Marine and Coastal Management - Linefish Dataset (First Semester of 2002) (AfrOBIS). 372 records from Agriculture and Agri-Food Canada, Saskatoon. 30150 records from Kashihara City Museum of Insect. 34326 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 42 records from Industriegebiet (Kempen). 1 records from Occurrence of mammalia relicts at site High Furlong. 15 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 200 records from Occurrence of mammalia relicts at site Grotte Scladina. 1 records from Range table from benthic foraminifers in ODP Hole 198-1207B. 293 records from EPOS3: SeaStars (Echinodermata, Asteroidea). 16907 records from ELM paleontology. 12158 records from Gunma Museum of Natural History, Insect Specimen. 3973 records from DBL_Life. 66 records from Benthic macrofauna abundance and biomass in surface sediment during cruise PLG93. 205 records from Fish Living in Freshwater (KIDR-PI). 3152 records from UAFMC Herps. 4 records from A new and presumably extinct species of Ptychochromoides (Teleostei: Perciformes: Cichlidae) from central Madagascar.. 2 records from (Table 4) Differences in king penguin (Aptenodytes patagonicus) colony arrivals and departures based on age, Possession Island. 7 records from Quadrige. 2 records from Coryphopterus kuna, a new goby (Perciformes: Gobiidae: Gobiinae) from the western Caribbean, with the identification of the late larval stage and an estimate of the pelagic larval duration.. 1801 records from Alterra (NL) - Entomofauna inventory in dead wood. 129 records from Mammalia (KNAM-MM). 3015 records from Bird specimens in Gifu Prefectural Museum. 92 records from Biotop Binsenwiesen (Wehrheim/Taunus). 34 records from Occurrence of mammalia relicts at site Felsdach Inzighofen. 16 records from Occurrence of mammalia relicts at site Risovaca. 3427 records from Occurrence of 13 crabeater seals (Lobodon carcinophaga) from ARGOS satellite track observations during campaign DRE1998. 1 records from Ueber Chilopoden aus westbalkanischen Hoehlen. 14522 records from MVZ Egg and Nest Collection (Arctos). 18 records from Redescription of two species of wobbegongs (Chondrichthyes: Orectolobidae) with elevation of Orectolobus halei Whitley 1940 to species level.. 172 records from Redescription of Gymnotus coropinae (Gymnotiformes, Gymnotidae), an often misidentified species of Neotropical electric fish, with notes on natural history and electric signals.. 1 records from The Oribatid Family Phthiracaridae I. Introduction and Redescription of Hoplophthiracarus pavidus (Berlese). 33 records from A redescription of the species of Eupolybothrus Verhoeff s. str. preserved in the British Museum (Natural History) and the Hope departement of Zoology Oxford (Chilopoda Lithobiomorpha). 1 records from Pelops ureaceus. 15768 records from SARCA. 1470 records from National Taiwan Museum. 1837 records from Cowan Tetrapod Collection - Herpetology. 6862 records from Hormigas del Museo de Entomología de la Universidad del Valle. 8006 records from Knerer collection / Gschwendtner property. 43443 records from Royal Museum of Central Africa - Albertian Rift Birds (ENBI wp13). 8332 records from Joint Nature Conservation Committee - Scotland Otter Survey Database. 1 records from Hoplophora laevigata. 36857 records from Environment Agency - Environment Agency Rare and Protected Species records v1. 14334 records from Merseyside BioBank - North Merseyside Other Taxa (unverified). 2391 records from Ohio State University Tetrapod Division - Reptile Collection (OSUM). 107 records from EcoRecord - Flatworm Records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 19309 records from Mammal collection, Natural History Museum, University of Oslo. 102 records from Kiesgruben Wemb. 86 records from Deponie Klausdorf. 31 records from Gelände der Lahntalschule Biedenkopf und Lahnauen. 7 records from VFD-RP: Taunus: Ponykoppel Thurner. 6 records from Faunal assemblage of sediment core GS7603-9. 55 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Rheidae. 9522 records from Fish collection, Natural History Museum, University of Oslo. 19 records from Mesozoa collection of National Museum of Nature and Science. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 99300 records from Landesmuseum Kärnten. 4 records from Taxonomy of Afrotropical and West Palaearctic ants of the ponerine genus Hypoponera Santschi (Hymenoptera: Formicidae).. 1 records from Pollen analysis of sediment profile KAIX_B from Kaiserwinkel. 20 records from University of Vienna, Institute for Botany - Herbarium WU. 9302 records from Ants from the Paraguayan dry Chaco. 5368 records from Dutch Mammal Society (NL) - Mammal observations extracted from historic reports. 837 records from Field Study Group of the Dutch Mammal Society (NL) - 2004 - Mammal Survey Rakitovec, Slovenia. 8 records from Five new species of the damselfish genus Chromis (Perciformes: Labroidei: Pomacentridae) from deep coral reefs in the tropical western Pacific.. 7410 records from Helgeland Museum, Lepidoptera. 11 records from A new species of Hemigrammus Gill, 1858 (Characiformes: Characidae) from Rio Caura, Venezuela.. 12 records from (Appendix B) Stratigraphic occurrence of radiolarian special and species groups in sediments of ODP Hole 199-1218A. 10 records from Naturschutzgebiet Ahrschleife (Altenahr). 27 records from Estetal (Buxtehude). 104 records from BIRDRACE Die Marburger-Vogelwelt.de radelt. 12 records from Wiesen am Treffpunkt Freizeit. 16 records from Wahner Heide LK 12 Biologie. 32 records from "Schwarzwassertal" bei Pobershau. 1 records from Total living benthic foraminifera at station M33/1_MC-13 (WAST-T), size fraction >30 µm. 4 records from Abundance of nematoda in sediment profile M3/1_012 from the Iberian deep sea basin (Table 5). 18 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/390-1a. 19296 records from The national database for marine data (MADS). 10 records from Flächennaturdenkmal Grubditz. 45 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Spheniscidae. 15 records from Taxonomy of European Damaeidae (Acari: Oribatida) I. Kunstidamaeus Miko, 2006, with comments on Damaeus sensu lato. 16 records from Taxonomic review of the genus Wasmannia.. 50 records from (Table 1) Biometrics of five seabird species from Kongsfjorden, Svalbard. 153 records from National Pine Marten Survey of Ireland 2005 - 2007. 3245 records from Distribution of barnacles, bivalves, gastropods, and calcified worm tubes in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 798 records from Biological Records Centre - Irish Otter Dataset. 37 records from CONN. 102 records from Birdrace-Westfälische-Nachtigallen-Recklinghausen. 42 records from Industriebrache (Kempen). 5 records from Gewässeruntersuchung (Prien) mit Kl. 4b. 161 records from BIRDRACE Nord-Seh-Team. 11 records from Aktion Wiese und Wegrain Gitzenheide. 7 records from Meiofauna abundance in sediment core 54301-010. 15 records from BIOTA Southern Africa - The Collection of Lichens at the Botanische Staatssammlung München. 145 records from Echinoderms in surface sediments off Sylt collected during Heincke cruise HE275. 74793 records from Natural History Museum Rotterdam (NL) - Mollusca collection. 18 records from (Figure 3) Distribution chart of dinoflagellate cysts of Cretaceous age from ODP Hole 103-638B. 7 records from Pollen profile III at Krumbach. 3 records from Pollen record of profile 1TZ1. 3898 records from Reptiles del Estado de Veracruz.. 3632 records from Bees of Canada / Joker's Hill collection. 92 records from (UTC-MO) University of Tennessee - Molluscs Collection. 67661 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1994) (AfrOBIS). 8 records from Faunal assemblage of sediment core GS7603-13. 2626 records from Biodiversity records from Ireland - general. 11 records from The interstitial subsoil fauna of the lower beach level at Sarso Beach, Red Sea (Table 4). 4 records from Die Bachspezies 2008/2009. 34 records from Parkuntersuchung Weißer See. 17 records from Fluss - Vielfalt. 30 records from Wasser-Lernort Nettemündung. 2427 records from Ibaraki Nature Museum, Mollusk collection. 2717 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Cirolana00/5. 1405 records from Fonoteca Zoológica, Museo Nacional de Ciencias Naturales, Madrid: FZ_AVES. 750 records from Museu Valencià d′Història Natural - Fundación Entomológica Torres Sala: FETS. 88 records from P. W. Lund collection in the National History Museum of Denmark, Copenhagen. 13708 records from Bohart Museum of Entomology, UCD. 1166 records from South Western Pacific Regional OBIS Data Bio Ross Subset (South Western Pac ific OBIS). 143 records from 4. Tag der Artenvielfalt, Naturschutzgebiet Hockenheimer Rheinbogen. 19 records from Occurrence of mammalia relicts at site Ochoz Cave. 17 records from Occurrence of mammalia relicts at site Kniegrotte. 5 records from Studies on the Zoarcidae (Teleostei: Perciformes) of the southern hemisphere. IX. A new species of Pachycara from the southwestern Atlantic.. 18 records from Nandus prolixus, a new species of leaf fish from northeastern Borneo (Teleostei: Perciformes: Nandidae).. 212557 records from South Australian Museum Australia provider for OZCAM. 3 records from Revision der Ceratozetidae, 3. Ceratozetes laticuspidatus n. sp. (Arach., Acari, Oribatei). 12506 records from ULg_Hexapoda. 10839 records from Bird skin collection, Natural History Museum, University of Oslo. 106 records from Regenrückhaltebecken (Zeulenroda). 24469 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Anfibios. 125 records from FFH-Gebiet Klosterwasser/Burkau. 6587 records from Ohio State University Tetrapod Division - Mammal Collection (OSUM). 110 records from Benthic macrofauna abundance of subcores of sediment core 13200-073. 198991 records from SysTax - Zoological Collections. 999 records from Biodiversidad y dinámica espacio-temporal del ictioplancton de dos sistemas lagunares de la Reserva de la Biósfera de Sian Ka'an. 7 records from Faunal assemblage of sediment core TR149-32. 78 records from (Appendix Table 1) Absolute abundances of benthic foraminifers in DSDP Hole 94-608. 3347 records from Mammal and Fish speciemens of Kumamoto City Museum. 152971 records from Insekten Sachsen. 5 records from Benthic macrofauna abundance of sediment core 13200-052. 6321 records from Colección de Anélidos Poliquetos del Pacífico Mexicano (UANL). 6255 records from Colección Ictiológica del Río Bravo en México (UANL). 1 records from Plant (NHMC-PL). 66 records from (Table 9) Distribution of ostracode species in surface sediments of the southern Laptev Sea. 20 records from Pollen profile Märchenwald B, Harz, Germany. 1414 records from Herpetofauna del corredor biológico Chichinautzin y la Sierra de Huautla en el estado de Morelos. 64240 records from The Scottish Ornithologists' Club - South East Scotland Tetrad Atlas 1988 - 1994 - non-sensitive breeding species. 667 records from Antarctic Krill occurrence data from Discovery expeditions. 228 records from LaBoOb02. 65 records from katzenbuckel. 69 records from Luch Niederlehme, Schüler der Klasse 7. 4 records from Klimaoasen in Köln. 64 records from Steinbruch Haas Stuttgart-Münster. 43 records from Occurrence of mammalia relicts at site Pestera Magura. 12147 records from Danish Ants (Formicidae). 143 records from Scottish Environment Protection Agency - Selected Scottish freshwater fish records from 2008-2011 (collected by SEPA). 64004 records from Environment Agency - Environment Agency freshwater invertebrate species (single species families). 3005 records from Colección Entomológica CDMB. 304 records from National Newt Survey. 1 records from Arthropoden aus südostalpinen Höhlen.. 10123 records from Wikander. 45815 records from Herpetology Collection - Royal Ontario Museum. 13 records from Cresswell Associates - Wildlife Surveys in Southern Scotland 2007-2011. 1 records from Deux especes nouvelles pour la science du genre Eupolybothrus Verhoeff (Lithobiomorpha: Ethopolinae). - Two new species for the science in the genus Eupolybothrus Verhoeff (Lithobiomorpha: Ethopolinae). 2805 records from Fundación Miguel Lillo - Colección Mamíferos. 1892 records from Physical properties and geochemical composition of sediment cores PTA02-04, PTA03-12 and PTA03-13 from Laguna Potrok Aike, Patagonia. 46 records from Matter enrichment of the macrofauna community of MAC station 12930-005. 87780 records from Norwegian Lepidoptera working group. 3312 records from Base de datos sobre ictioplancton para la Bahía de Campeche, México. 1 records from Inventario florístico y base de datos de la Reserva Ecológica Sierra de San Juan, Nayarit, México. 4 records from Akita Prefectural Museum＋Annelids Specimens of Akita Prefectural Museum. 415268 records from RBINS collections. 126 records from Fig. 4. Simplified macrofossil concentration in sediment core Lz1116. 59406 records from PIROP (Shipboard Surveys). 10 records from United States National Plant Germplasm System Collection. 1796 records from Sea shell specimens database of Mr. Toru Ueda collection, Shizuoka Prefecture Museum of Natural History. 82 records from Langes Tannen. 1 records from Planktic foraminifera abundance of Hole 62-465. 5 records from Planktic foraminifera abundance of Hole 74-525A. 1 records from Planktic foraminifera abundance of Hole 74-527. 20 records from Biological Records Centre - RISC Non-Native Species Records for Rhododendron Leafhopper. 1 records from Herbarium specimens of Institut Scientifique Mohamed V university (RAB). 16 records from Two new emerald geometrid species of Telotheta Warren from Ecuador and Bolivia (Lepidoptera: Geometridae, Geometrinae, Lophochoristini). 364 records from Revision of the genus Draconarius Ovtchinnikov 1999 (Agelenidae: Coelotinae) in Yunnan, China, with an analysis of the Coelotinae diversity in the Gaoligongshan Mountains. 166 records from RSPB - Redshank nesting on saltmarshes in Britain (RSPB). 7 records from University of British Columbia Herbarium (UBC) - Fungi Collection. 55 records from A taxonomic revision of the Pheidole roosevelti-group (Hymenoptera: Formicidae) in Fiji.. 2 records from High-resolution X-ray computed tomography of an extant new Donuea (Araneae: Liocranidae) species in Madagascan copal. 7 records from Peckoltia sabaji, a new species from the Guyana Shield (Siluriformes: Loricariidae).. 412 records from Reptilia Collection of Museum and Institute of Zoology PAS. 466 records from Macrobenthos in surface sediments off Sylt collected during Heincke cruise HE275. 2 records from (Table 8) Relative abundance of benthic foraminifera in ODP Hole 112-682A, Part IV. 105 records from (Table 3) Meiofauna density in surface sediments of the Cretan Sea. 34315 records from Historical hyperbenthos data (1987-2001) from the North Sea and some adjacent areas (EurOBIS). 85439 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1987) (AfrOBIS). 25333 records from Western Palearctic migratory birds in continental Africa. 40 records from Animal observations. 3645 records from Insects specimen database of Osaka Museum of Natural History. 4 records from Espèces vasculaires endémiques et orchidées (CITES). 35 records from Westerwälder Umwelt- und Naturschutztag an der Fuchskaute im Westerwald. 1462 records from Avifauna en dos parches de bosque seco del departamento del Valle Cauca (Colombia). 593 records from Mamíferos voladores laguna El Tinije. 1030 records from Royal Botanic Gardens, Kew - Herbarium Specimens. 6 records from Ecofact. 778 records from Gloucestershire Centre for Environmental Records - Gloucestershire BAP Priority Species: Great crested newts. 1 records from Fundacin Miguel Lillo - Coleccin Fanerogmica. 4102 records from Coleoptera collection (EC) of the Muséum national d'Histoire naturelle (MNHN - Paris). 98 records from RSPB - Twite national sample survey in the UK in 1999 (SCARABBS). 2 records from Die Myriopodenfauna von Albanien und Jugoslavien. 11 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC02. 3 records from Nationalpark Harz Juniorranger. 30 records from Schulgelände Lise Meitner Realschule (Paderborn). 105 records from BIRDRACE coesfelder_vogelkundler. 89 records from BIRDRACE Uttenreuther Spatzenzähler. 37 records from Aktionstag "Artenvielfalt der Feuchtwiesen bei Daubringen". 3 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC SC2-L, size fraction >150 µm. 17155 records from MZFC/Coleccion de Aves. 87 records from Countryside Council for Wales - Great Crested Newt SAC Monitoring Data. 72 records from Nematode densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC03. 60 records from crocodylus. 335 records from Revision of the South American freshwater genus Plagioscion (Teleostei, Perciformes, Sciaenidae).. 146 records from (Table 2a) Abundance of macrobenthos species in samples from Cruise AMK54 stations in the Novaya Zemlya Trough. 15587 records from MSB Host Collection (Arctos). 100 records from National Biodiversity Network Trust - Demonstration dataset for record commenting on the NBN Gateway. 1 records from On the Chilopoda from Turkey. 20187 records from Alterra (NL) - Entomofauna inventory in riverside grasslands. 2 records from The first record of a fly of the family Milichiidae (Diptera) interacting with an ant of the genus Polyrhachis Smith, 1857 (Hymenoptera: Formicidae). 3 records from A Partial Revision of the Genus Metabelba Grandjean (Oribatei, Acarina). 1626 records from Ornithologie ZMK. 674 records from Field Study Group of the Dutch Mammal Society (NL) - 2012 - Mammal Survey Galicia, Spain. 8359 records from Natural England - Batsites inventory for England. 39 records from Varnhalt. 39 records from Biodiv-Camp Sandmagerrasen in Nürnberg/Langwasser. 46 records from (Table 4) Biomass of (benthic) amphipods in the Bering and Chukchi seas. 2 records from Die Bachspezies. 27 records from Liether Park (LMS), 5a. 208 records from MfN - Fossil invertebrates IIa. 6 records from KTU Pinophyta. 2 records from Ostracoda abundance of Hole 13-129. 9 records from Benthic macrofauna abundance of sediment core 13200-075. 11 records from Tab. 3: Stomach contents of Knots of Hazen Camp. 17 records from Molluscs in surface sediments off Sylt collected during Heincke cruise HE275. 1627 records from Crustáceos estomatópodos, anfípodos, isópodos y decápodos del litoral de Quintana Roo. 1 records from Benthic hard-bottom communities abundance at X-Huinay in 2010. 1229 records from Insect Collection (CeStuBio). 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 58 records from Mamíferos laguna El Tinije. 31748 records from Colección Nacional de Aracnología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 1 records from Études myrmécologiques en 1886.. 12109 records from Inventario de fauna presente en la jurisdicción de Corantioquia. 4 records from (Table 4) Benthic foraminifera in Northwest Indian Ocean surface sediments. 2 records from Vermes ZMK. 161 records from John Muir Trust - Species Records for John Muir Trust Properties Nevis, Sandwood, Quinag and Schiehallion 2010.. 65334 records from Bedfordshire and Luton Biodiversity Recording and Monitoring Centre - Bedfordshire Micro Moths (BNHS) - 1820-2009. 19 records from Hecke - Klassen 2 a und 2 b VS Tussenhausen. 110 records from Föhrenried (Fronreute und Baindt). 6 records from Kindergarten. 5 records from Warnowufer Groß Klein. 410973 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Aves Reproductoras. 188 records from Schatzinsel Wangerooge. 37 records from Tornoer Teich. 12 records from Sonntagmorgen-Veranstaltungen im Zeichen des GEO-Tags. 1040 records from Anfibios y Reptiles reportados en humedales del departamento de Córdoba. 34 records from Marine Conservation Society - Palinurus elephas or Crawfish sightings in the UK and Ireland from 1969 to the present time.. 8 records from (Table B) Abundance of benthic fauna associated with shrimp swarms at hydrothermal fields on the Mid-Atlantic Ridge. 12 records from Dispatch from the field: ecology of ground-web-building spiders with description of a new species (Araneae, Symphytognathidae). 1575 records from Porifera MZS. 304 records from Lice (Phthiraptera) of Ireland. 36432 records from RSPB - Corncrake national surveys - raw data (SCARABBS). 3 records from First report of the genus Conostigmus Dahlbom (Hymenoptera: Ceraphronoidea: Megaspilidae) from India with description of a new species. 102 records from Review of the Nearctic genus Scyletria Bishop & Crosby (Araneae, Linyphiidae), with a transfer of S. jona to Mermessus O. Pickard-Cambridge. 1326 records from Colección de Invertebrados Cenpat (CNP-INV). 16568 records from Inventaire National du Patrimoine Naturel : Données des campagnes de Suivi Aérien de la Mégafaune Marine (SAMM) de France métropolitaine. 432 records from Royal Horticultural Society - RHS Hemerocallis gall midge (Contarinia quinquenotata) monitoring . 127273 records from mel. 66 records from Hainhoop - Tonkuhle - Bullenmoor (Arpke). 28 records from "Schwarzes Teich" (Waldpark Radebeul). 24 records from Schulgartengelände des Hans-Carossa-Gymnasiums (Berlin). 12 records from ISTOTA - Schulgarten in Krakau, Stadtteil Ludwinow. 36 records from Landschaftsschutzgebiet Schmutterwald. 114 records from BIRDRACE Di-Bi-Di-Birder. 61 records from BIRDRACE Baumläufer. 110 records from BIRDRACE Linumer Luchschleicher. 443 records from (Appendix 1) DSDP Site 94-607 ostracode species census data. 12 records from Benthic macrofauna abundance of sediment core 13200-047. 29 records from Familientag am Schorberg. 1572 records from Lepidoptera - SNSD. 429 records from Larval fish at Helgoland Roads in 2004. 10 records from Pollen analysis of sediment core GeoB1007-4. 2790 records from Inventario Fauna Vertebrada de la Manchuela Conquense (CUENCA), 2007. Asociación de Desarrollo Integral de la Manchuela Conquense (ADIMAN). 4 records from Akita Prefectural Museum＋Specimens of Class Maxillopoda of Akita Prefectural Museum. 1208 records from Cetacean Sightings Survey and Southern Ocean cetacean program. 3824 records from Laboratório de Ecologia e Biogeografia de Insetos da Caatinga. 272 records from Relative abundance of ostracods in sediment core Co1202. 20 records from Artenvielfalt auf Restbauernhof. 38 records from Spandau HBO. 134 records from Birdrace-Raumpatrouille_Oriolus-Münster. 53 records from Occurrence of mammalia relicts at site Spitalhöhle. 14 records from Lauchhamer GEO-Tag der Artenvielfalt. 7 records from NW-Innenhof Gesamtschule Herten 7.6.2001. 334 records from BIRDRACE Cuxland - Schwenke Geo Consult. 192 records from Alterra (NL) - Microarthropods inventory in Cranendonck area. 8 records from Meiofauna abundance in sediment core 13077-060. 9 records from Benthic macrofauna abundance of sediment core 12930-028. 6 records from Benthic macrofauna abundance of sediment core 13077-098. 11 records from Benthic macrofauna abundance of sediment core 13201-002. 4824 records from Echigo-Matsunoyama Museum of Natural Science, Usuke Shiga butterfly collection. 43 records from Centre dEstudis Avancats de Blanes. Limnological Observatory of the Pyrenees. 86154 records from Naturalis Biodiversity Center (NL) - Coleoptera. 22700 records from Royal British Columbia Museum. 1824 records from CNAN/Scorpiones. 2 records from Die Myriopodenfauna von Albanien und Jugoslavien. 6 records from Spider hosts (Arachnida, Araneae) and wasp parasitoids (Insecta, Hymenoptera, Ichneumonidae, Ephialtini) matched using DNA barcodes. 5 records from Observation of birds at station PS14/152 along 49° West. 212 records from Lustadter Wald .. 1 records from Abundance of benthos infauna at station GIK23037-3. 454 records from Colección de Entomología - Hymenoptera - Aculeata. 3772 records from BOS Arthropod Collection of University of Oviedo (Spain): Opiliones. 4 records from RSPB - Black grouse lek survey in Wester Ross and Skye 2009 (RSPB). 1 records from Zetes dorsalis. 4316 records from Diptera Collection of Museum and Institute of Zoology PAS. 239 records from Systematic review of the neotropical shovelnose catfish genus Sorubim Cuvier (Siluriformes: Pimelodidae).. 50409 records from MSU Mammalogy, Ornithology and Vertebrate Paleontology Collections. 400 records from Colección Hidrobiológica del Chocó. 42 records from (Fig. 4) Relative proportions of the most abundant chironomid taxa in the Lake Temje sediment core. 9 records from Aktion der Klasse H2 in Simmelsberg. 8 records from Flora und Fauna am Mühlberg. 68 records from Numbers and weights of nematodes from from surface sediments of the Iberian deep sea basin (Table 7). 173 records from Coleoptera identified from the Woolwich Manor Way site, Becton, London. 102 records from (Table 5) Ostracod assemblages of sediment core 9407. 52 records from (Appendix B) Nannofossil abundances in DSDP Hole 90-594 from the South Chatham Rise, southeastern New Zealand. 117 records from Benthic macrofauna abundance of subcores of sediment core 12930-065. 904 records from (Table 3) Ostracoda abundances in sediment core PS2200-5 (Morris Jesup Rise). 8 records from (Table 3) Relative abundances of benthic foraminifera in ODP Hole 117-728A. 213 records from Amphibian and Reptile (JNHM-AR). 999 records from (Table A-2.1 to A-2.7) Abundance of macrobenthos in surface sediments in the Arctic Ocean. 8307 records from Southern Ocean octopus. 29002 records from Computarización de la Colección Nacional de insectos Dr. Alfredo Barrera Marín del Museo de Historia Natural de la Ciudad de México. Coleóptera. 760 records from Arthropoda specimens of Toyama Science Museum. 3 records from Meiofaunal abundance, biomass, taxon richness and indices of nematode diversity of samples from the Santa Maria di Leuca Bank (southern Adriatic margin). 1575 records from Collection Ornithologie - SNSD. 377929 records from ``South Western Pacific Regional OBIS Data provider for the NIWA Marine Biodata Information System``. 55256 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 2000) (AfrOBIS). 77301 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1999) (AfrOBIS). 6 records from HBGSpermatophyta - Herbarium Hamburgense. 195264 records from U.S.D.A. Forest Service, Redwood Sciences Laboratory - Lamna Point Count. 80846 records from Colección de Lepidópteros del Museo de Zoología 'Alfonso L. Herrera', México (MZFC, UNAM). 94 records from Integrierte Gesamtschule Flensburg Wiemoosgraben. 103 records from Weidenhüttendorf an der Würm (München). 3653 records from A Dataset of Deep-Sea Fishes Surveyed by Research Vessels in the Waters around Taiwan. 64 records from Occurrence of mammalia relicts at site Vindija. 24 records from Occurrence of mammalia relicts at site Nikolaushöhle. 25 records from Description of three new species of the genus Chromaphyosemion Radda, 1971 (Cyprinodontiformes: Nothobranchiidae) from the coastal plains of Cameroon with a preliminary review of the Chromaphyosemion splendopleure complex.. 2427 records from Base de datos y colección de distintos grupos del zooplancton de regiones marinas prioritarias de Jalisco y Colima en el Pacífico mexicano. Larvas de Peces. 735 records from Diversidad de coleópteros scarabaeoidea del estado de Puebla (I). 1794 records from Elephant Seal Sightings, Heard Island. 6170 records from Meiobenthos of subtidal sandbanks on the Belgian Continental Shelf (EurOBIS). 15 records from Angelberger Forst - Klassen 3 a und 3 b. 331 records from Artenvielfalt der Nordsee - Bremerhaven (Dorum-Neufeld). 15555 records from Biological Records Centre - Coccinellidae Data. 1 records from Arthropoden aus südotsalpinen Höhlen gesammelt von Karl Strasser. 4. Aufsatz. 2193 records from Hemiptera (Homoptera) collection of National Museum of Nature and Science. 1 records from Notizen über Oribatei (Acari). III. 55 records from Two new species of the scorpionfish genus Trachyscorpia (Sebastidae: Sebastolobinae) from the southern Indo-West Pacific, with comments on the distribution of T. eschmeyeri.. 37881 records from Bird Collection of Museum and Institute of Zoology PAS. 610 records from RSPB - Farmland bird database in Dumfries and Galloway, 1999-2010 (RSPB). 1274 records from Collection of Heteroptera. 8585 records from RSPB - Bird Conservation Targeting Project (BCTP) in the UK, archived data (2001-2008) - sensitive records. 372 records from El efecto de la variación ambiental en la diversificación de anfibios y la prevalencia de su patógeno mortal: Un transecto por los humedales desde el Magdalena Medio hasta la Orinoquía. 2413 records from Literature based species occurrence data of birds of North-East India. 83 records from Birdrace-Die_Vogelscheuchen-Herford. 17 records from Tierpark Zittau. 11 records from Revalidation of Pterinopelma Pocock 1901 with description of a new species and the female of Pterinopelma vitiosum (Keyserling 1891) (Araneae: Theraphosidae: Theraphosinae). 28 records from Naturpark Kottenforst-Ville 15.6.09. 5 records from Herbier de Wallis et Futuna. 1212 records from RMT Trawl catch from the 1990/91 V6 AAMBER2 voyage. 48 records from Echinoderms in surface sediments off Sylt collected during Heincke cruise HE218. 86 records from Abundance of macrobenthos organisms in the northern Wadden Sea in 2008. 3 records from Akita Prefectural Museum＋Echiurans Specimens of Akita Prefectural Museum. 44498 records from Canadian National Collection (CNC) of Insects, Arachnids and Nematodes. 43 records from Nekton and plankton counts from Wechselnetz-Hai (300 µm) hauls of cruise GAE 1975/76. 26686 records from Ontario Nest Records. 4722 records from Insect Specimens of Taga Town Museum, Shiga Pref., Japan. 325 records from Zukünftiges NSG Höftland/Bockholmwik. 13 records from Occurrence of mammalia relicts at site Steinheim an der Murr. 19 records from Waldstück am Schullandheim Bad Bederkesa. 66 records from Klostergarten St Luzen. 534 records from Leopard Seal census, Heard Island 1987/88. 8611 records from Collection Herpetology SMF. 607 records from King penguin census data, Gadget Gully, Macquarie Island (1993-2008). 23643 records from CNIN/Abejas de México/Apoidea. 7 records from (Table 4a) Miocene biostratigraphy of the Reinbekian stage in Schleswig-Holstein. 8 records from Orchid Herbarium Collection. 3 records from (Table 2) Mercury concentration in hair of Northwest Greenland polar bears (Ursus maritimus). 11648 records from Visfauna - Juvenile and adult fishes in riparian habitats along the river Yser. 20 records from Marine gastropods and other remains profile from sediment core AV14_K2-3. 2395 records from Type Specimen Database of Museum and Institute of Zoology PAS. 1 records from Beitrag zur Kenntnis der Höhlen-Oribatiden der Schweiz (Acari: Oribatida) (Neue und interessante Milben aus dem Genfer Museum LI). 2898 records from Hymenoptera collection (EY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 2 records from Note tassonomiche e faunistiche su Chilopodi della Grecia (Chilopoda). 38522 records from Escarabajos Coprófagos (Coleoptera: Scarabaeinae) de la Colección Entomológica del Instituto Alexander von Humboldt. 2876 records from Naturalis National Natural History Museum (NL) – Mollusca fossils. 16 records from Malakologie ZMK. 161 records from Meiofaunal abundance in sediments obtained during RRS Charles Darwin cruise CD179. 36351 records from Naturalis National Natural History Museum (NL) – Crustacea_Decapoda. 56 records from Herbarium Senckenbergianum (FR). 177 records from Benthic meiofauna abundance in surface sediment of core PLG93_BCORE7. 89 records from Dixidae (Diptera) of Ireland. 116 records from Polychaeta abundance in surface sediments of the east Greenland continental slope (75° N section). 4 records from (Table 1) Mean age, body measurements, and body condition index of polar bear (Ursus maritimus) mothers and cubs. 164 records from Terrestrial molluscs at the Natural Park of the Serralada Litoral (Barcelona, Spain). 1 records from A new species of Tyrannomyrmex (Hymenoptera: Formicidae: Myrmicinae) from India.. 11 records from (Tables S1,2) Stable isotopes in muscle tissue of polar bears (Ursus maritimus) from various regions of the Arctic. 289 records from Odonata del Museo de Entomología de la Universidad del Valle. 845 records from Alterra (NL) - Entomofauna inventory in arable fields Hoeksche Waard. 1 records from Eine Milbendiagnose aus dem Nachlass Dr. Josef Schweizer. 988 records from Museum TwentseWelle (NL) - Fossil Collection. 36 records from Ecsenius caeruliventris and E. shirleyae, two new species of blenniid fishes from Indonesia, and new distribution records for other species of Ecsenius.. 18 records from (Table 1) Beluga (Delphinapterus leucas) density and abundance, and pod characteristics in west Greenland waters. 1373036 records from Suffolk Biological Records Centre - Suffolk Biological Records Centre (SBRC) dataset. 8928 records from City of Amsterdam (NL) - Fyke Fishing Piet Ruiter. 3650 records from Coelenterata (Cnidaria and Ctenophora) collection of National Museum of Nature and Science. 100 records from Royal Horticultural Society - Nezara viridula records held by the Royal Horticultural Society. 28658 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mammalia. 2212 records from RIVM (NL) - Earthworm Observations in Soil Samples. 1 records from Dolistenus menozzii n. sp. della famiglia Platydesmidae (Miriapodi Colobognati); e altri miriapodi della Calabria. 464 records from Lepidoptera collection, NTNU, Trondheim. 16 records from Amtsrain Apolda-Zottelstedt. 44 records from Schafheide im Böblinger Wald. 30 records from (Table 3) Distribution of benthic foraminifers at DSDP Hole 21-206. 50 records from Mean density of total metazoan meiofauna and major taxa or groups in the top 10 cm of surface sediment on 25 different dates at DYFAMED station. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 1042 records from Field Study Group of the Dutch Mammal Society (NL) - 2003 - Mammal Survey Alvao Natural Park, Portugal. 1 records from Arthropoden aus südostalpinen Höhlen.. 8 records from Cirrhigaleus australis n. sp., a new Mandarin dogfish (Squaliformes: Squalidae) from the south-west Pacific.. 31 records from Description of Cathorops mapale, a new species of sea catfish (Siluriformes: Ariidae) from the Colombian Caribbean, based on morphological and mitochondrial evidence.. 5 records from Cnesterodon holopteros (Cyprinodontiformes: Poeciliidae: Poeciliinae), a new species from the Republic of Uruguay.. 83 records from BIRDRACE Die Frankenpfeifer. 8 records from Teich im Wald zwischen Böblingen und Schönaich. 6 records from Faunal assemblage of sediment core TR149-38b. 26 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/313-1. 21 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/356-1. 9154 records from MfN - Fossil invertebrates IIb. 1930 records from Spiders of Ireland. 104 records from Coarse fraction analysis and texture of biogenous sands from Great Meteor Seamount surface samples (Table 1). 8 records from Meiofauna abundance in sediment core 12930-075. 18092 records from MSB Parasite Collection (Arctos). 729 records from (Table 2) Occurrence of ostracoda in surface sediments of the Arctic Ocean. 36 records from Ober-Olmer Wald 09. 6 records from Multivariate discrimination and description of a new species of Tapinoma from the Western United States.. 8 records from Phoronida - SMF. 5 records from Pollen profile II/B at Krumbach, Germany. 1222 records from Ichneumonidae (Hymenoptera) de la reserva de la biosfera El Cielo, Tamaulipas. 23 records from Two new species of Pseudolaguvia (Teleostei: Erethistidae) from Bangladesh.. 1400 records from Historia natural del parque ecológico estatal de Omiltemi, Chilpancingo, Guerrero, México. 4000 records from Mollusk Collection of Yokosuka City Museum. 46669 records from IG TUT paleontology. 16 records from (Table 2) Madreporarian corals collected in the Canary upwelling area. 1 records from Pelops tardus. 83094 records from Mammal specimens. 1 records from Herbarium Willing. 642 records from Insect colletion. 30 records from Lower Albian Moriez core (Niveau Paquier) individuals per gram sediment of benthic foraminifera, in SE France. 3 records from Faunal assemblage of sediment core TR149-34. 3 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/314-1. 2 records from Aktion des Romain-Rolland-Gymnasiums. 381 records from Schatzinsel Norderney. 3256 records from Distribution of diatoms and ostracods in sediment samples collected between
Keywords: GBIF; biodiversity; species occurrences